Perovskite-based laminated solar cell, preparation method and power utilization device
By setting up perovskite light absorbing layers with different band gaps in perovskite solar cells and forming non-smooth concave grooves and convex ridges on the surface of the first perovskite layer, the problem of limited efficiency improvement of traditional solar cells is solved, and a higher short-circuit current density and photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202311435187.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The improvement of photoelectric conversion efficiency of traditional single-junction perovskite solar cells is limited by theoretical limits. How to further improve the short-circuit current level of the device is an important research direction for improving performance.
By providing a perovskite absorbing layer with different band gaps in the stacked solar cell, and a non-smooth surface, including the morphology of the concave grooves and convex ribs, is provided in the laminated solar cell, on one side surface of the first perovskite layer, close to the carrier composite layer, the non-smooth surface forms an elongated concave-convex interface with the adjacent surfaces of the adjacent structural layer.
This technical method can fully absorb photons in different bands, reduce thermal relaxation losses, improve utilization of incident light, increase short-circuit current density, and improve photoelectric conversion efficiency.
Smart Images

Figure CN119923071A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a stacked solar cell, a preparation method and an electrical device, and further to a perovskite-based stacked solar cell, a preparation method and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] Perovskite solar cells are devices that use the photoelectric conversion mechanism of perovskite crystal materials to convert solar energy into electrical energy. They are the third generation of solar cells. They have many advantages such as high photoelectric conversion efficiency, simple manufacturing process, and low production cost. They have been widely studied in recent years. However, the improvement of the photoelectric conversion efficiency of traditional single-junction perovskite solar cells is limited by theoretical limits. Tandem solar cells can expand the absorption spectrum of solar cells by superimposing semiconductors with different band gaps, converting light energy into electrical energy to a greater extent. It is an important way to overcome the efficiency of single-junction cells Shockley-Queisser limit and an important strategy to improve the photoelectric conversion efficiency of solar cells in the future. For perovskite-based tandem solar cells, how to further improve the short-circuit current level of the device is one of the important research directions for improving device performance. Summary of the invention
[0004] In view of the above problems, the present application provides a perovskite-based tandem solar cell, a preparation method and an electrical device. The perovskite-based tandem solar cell includes a perovskite light-absorbing layer, which can provide a higher short-circuit current density and is also conducive to improving the photoelectric conversion efficiency.
[0005] In a first aspect of the present application, a perovskite-based tandem solar cell is provided, wherein the tandem solar cell comprises a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence, wherein the first perovskite subcell comprises a first perovskite layer, and the second perovskite subcell comprises a second perovskite layer; the band gap of the first perovskite layer is different from the band gap of the second perovskite layer;
[0006] Wherein, the thickness direction of the first perovskite layer is recorded as the longitudinal direction;
[0007] The surface of the first perovskite layer on one side close to the carrier recombination layer is a non-smooth surface, the non-smooth surface is provided with concave grooves, and convex edges are formed between at least a portion of adjacent concave grooves;
[0008] The stacked solar cell meets at least one of the following characteristics:
[0009] At least a portion of the concave grooves have different widths at at least a portion of the depth positions;
[0010] At least a portion of the ridges have different widths at at least a portion of their heights.
[0011] By providing perovskite light-absorbing layers with different band gaps in the stacked solar cell, photons of different wavelengths can be fully absorbed, thermal relaxation losses can be reduced, and the utilization rate of incident light can be improved. A non-smooth surface including concave grooves and convex ridges can be provided on the surface of one side of the first perovskite layer close to the carrier recombination layer, so that the non-smooth surface and the adjacent surface of the adjacent structural layer form a long strip-shaped concave-convex interface, which can be recorded as the first interface. When at least one of the two characteristics of "at least a portion of the concave grooves have different widths at at least a portion of the depth position" and "at least a portion of the convex ridges have different widths at at least a portion of the height position" is met, at least a portion of the photons incident on the first interface can experience at least one of multiple refractions and multiple reflections at the first interface. For photons directed toward the first interface, compared with the situation in which a traditional smooth interface is only reflected and / or refracted once after contacting the interface, the non-smooth first interface in the present application can increase the contact opportunity between the photons and the first interface, increase the probability of the photons being captured by the perovskite layer in the perovskite-based tandem solar cell, and increase the efficiency of light utilization; for photons that are not absorbed by the first perovskite layer and are directed toward the first interface, the probability of the photons entering the second perovskite layer can be increased, thereby increasing the number of photons in the absorbable band of the second perovskite layer; for photons that are still not absorbed by the second perovskite layer and are directed toward the first interface, the probability of entering the first perovskite layer can be increased, thereby increasing the number of photons in the absorbable band of the first perovskite layer. Therefore, the overall current level of the tandem solar cell can be improved, the short-circuit current density can be improved, and in addition, it is also beneficial to improve the photoelectric conversion efficiency.
[0012] Based on any suitable embodiment in the present application, in some further embodiments, the morphologies of the interfaces formed by different structural layers between the first perovskite layer and the second perovskite layer are substantially matched.
[0013] When the morphologies of the interfaces formed by different structural layers between the first perovskite layer and the second perovskite layer are basically matched, the different structural layers have uniform thicknesses. At this time, the surface of the second perovskite layer close to the first perovskite layer can form a non-smooth surface with a similar morphology. Corresponding to the "convex-concave" interface on the surface of the first perovskite layer, a corresponding "convex-concave" interface (referred to as the second interface) can be formed on the surface of the second perovskite layer. The second interface is also beneficial to increase the number of absorbable wavelength photons and light utilization rate in the perovskite layer in the stacked solar cell, which is beneficial to improving the overall current level of the stacked solar cell and the photoelectric conversion efficiency.
[0014] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0015] The width of at least a portion of the ridges is 0.5 μm to 4 μm, and can be further 2 μm to 3.5 μm;
[0016] The half-height width of at least a portion of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm;
[0017] The height of at least a portion of the ridges is greater than or equal to 100 nm, and may further be 100 nm to 250 nm;
[0018] In at least a portion of the non-smooth surface, the average width of the ridges is 0.5 μm to 4 μm, and may be further 2 μm to 3.5 μm;
[0019] In at least a portion of the non-smooth surface, the average half-height width of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm;
[0020] In at least a portion of the non-smooth surface, the average height of the ridges is 100 nm to 500 nm, and may be 100 nm to 250 nm;
[0021] Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is greater than or equal to 0.1 mm 2 , further optional to be greater than or equal to 0.6mm 2 .
[0022] By adjusting one or more parameters of the width, half-width, height of the ridges and the average values of these parameters, the probability of photons emitted from the inside of the first perovskite layer to the first interface after being reflected multiple times at the ridge interface of the first perovskite layer can be adjusted. By controlling the above one or more parameters within the above range, more photons are absorbed by the second perovskite layer, which is conducive to enhancing the utilization rate of photons that are not absorbed after passing through the first perovskite layer. These photons may include photons in the absorbable band of the second perovskite layer, so the short-circuit current density can be better improved, and it is also more conducive to improving the photoelectric conversion efficiency of the stacked solar cell. The photons emitted from the side of the first perovskite layer to the first interface can come from external incident light.
[0023] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0024] The width of at least a portion of the concave grooves is less than or equal to 1.2 μm, and may be 0.5 μm to 1 μm;
[0025] The half-height width of at least a portion of the concave grooves is less than or equal to 1 μm, and can be optionally 0.2 μm to 0.7 μm;
[0026] The depth of at least a portion of the concave grooves is greater than or equal to 100 nm, and can further be 100 nm to 250 nm;
[0027] The aspect ratio of at least a portion of the concave grooves is 0.03 to 0.5, and can be further 0.25 to 0.35;
[0028] In at least a portion of the non-smooth surface, the average width of the concave groove is 0.3 μm to 1 μm, and can be 0.5 μm to 1 μm;
[0029] In at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.2 μm to 0.7 μm, and can be 0.3 μm to 0.55 μm;
[0030] In at least a portion of the non-smooth surface, the average depth of the concave groove is 100nm to 500nm, and can be 100nm to 250nm;
[0031] In at least a portion of the non-smooth surface, the average depth-to-width ratio of the concave groove is 0.03 to 0.5, and can be further 0.25 to 0.35;
[0032] Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is greater than or equal to 0.1 mm 2 , further optional to be greater than or equal to 0.6mm 2 .
[0033] By adjusting one or more parameters of the concave groove width, half-height width, depth, aspect ratio and the average value of these parameters, the probability of photons emitted from the second perovskite layer side to the first interface entering the first perovskite layer at the concave groove interface of the first perovskite layer can be adjusted. By controlling the above one or more parameters within the above range, the optical path of the photons that are not absorbed after the interface reflection of the second perovskite layer is significantly increased in the first perovskite layer, and more photons can be absorbed by the first perovskite layer. This part of the photons may include photons in the absorbable band of the first perovskite layer, so that the light utilization rate can be improved, thereby better improving the overall current level and improving the photoelectric conversion efficiency of the stacked solar cell. Among them, the photons emitted from the second perovskite layer side to the first interface can come from the reflected light at the second electrode.
[0034] By comprehensively adjusting the width and length of the concave groove, the proportion of the longitudinal projection area of the concave groove in the longitudinal projection area of the first perovskite layer can be adjusted. The higher the proportion, the more significant the comprehensive improvement effect of the concave groove on the overall current level and photoelectric conversion efficiency. The longitudinal projection area of the first perovskite layer can be regarded as being substantially equal to the longitudinal projection area of the non-smooth surface. Therefore, the proportion of the longitudinal projection area of the concave groove in the longitudinal projection area of the first perovskite layer is substantially equal to the percentage of the sum of the longitudinal projection areas of the concave groove relative to the longitudinal projection area of the non-smooth surface.
[0035] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0036] In at least a part of the non-smooth surface, the average spacing of the ridges is 1 μm to 20 μm, and can be 10 μm to 20 μm;
[0037] In at least a portion of the non-smooth surface, the average spacing of the concave grooves is 1 μm to 20 μm, and can be 10 μm to 20 μm;
[0038] The half-height width of at least a portion of the convex ridges is greater than the half-height width of the adjacent concave grooves;
[0039] In at least a portion of the non-smooth surface, the ratio of the average half-height width of the convex ridges to the average half-height width of the concave grooves is 1 to 6, and can further be 4 to 5;
[0040] In at least a portion of the non-smooth surface, the ratio of the sum of the half-height cross-section areas of the ridges to the sum of the half-height cross-section areas of the concave grooves is 1 to 36, and may further be 10 to 30;
[0041] In at least a portion of the non-smooth surface, the sum of the projection areas of the concave grooves along the longitudinal direction accounts for 5% to 95% of the projection area of the non-smooth surface along the longitudinal direction, and may further be 5% to 50%;
[0042] Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is greater than or equal to 0.1 mm 2 , further optional to be greater than or equal to 0.6mm 2 .
[0043] By adjusting one or more parameters of the average spacing of the ridges, the average spacing of the concave grooves, the ratio of the average half-height width of the ridges to the average half-height width of the concave grooves, and the ratio of the sum of the areas of the half-height cross-sections of the ridges to the sum of the areas of the half-height cross-sections of the concave grooves, the density of the concave grooves and / or the ridges on the non-smooth surface of the first perovskite layer can be adjusted, and the unevenness of the non-smooth surface can be adjusted, thereby adjusting the degree of improvement of the photoelectric conversion effect. By controlling one or more of these parameters within the above range, the concave-convex morphology of the first interface can be fully utilized to make the first perovskite layer and / or the second perovskite layer absorb more photons, which is more conducive to improving the short-circuit current density. In addition, it can also be more conducive to improving the photoelectric conversion efficiency. When external incident light is incident from the first electrode, by controlling the half-height width of at least a portion of the ridges to be greater than the half-height width of the adjacent concave grooves, it is conducive to more photons that are not used by the first perovskite layer in the photons that are initially incident on the first interface Enter the second perovskite layer.
[0044] Based on any suitable embodiment of the present application, in some further embodiments, the opening width of at least a portion of the concave grooves is greater than the bottom width;
[0045] Optionally, based on the proportion of the projected area of the concave grooves along the longitudinal direction, at least 50% of the opening widths of the concave grooves are greater than the bottom widths; further optionally, at least 80% of the opening widths of the concave grooves are greater than the bottom widths;
[0046] Optionally, based on the proportion of the projected area of the concave groove along the longitudinal direction, the opening width of at least a portion of the concave grooves is greater than the half-height width and the bottom width; further optionally, at least 50% of the concave grooves have an opening width greater than the half-height width and the bottom width; further optionally, at least 80% of the concave grooves have an opening width greater than the half-height width and the bottom width.
[0047] When the concave groove as a whole has a cross-sectional shape of "wide at the top and narrow at the bottom", at this time, the opening width of the concave groove is greater than the bottom width. Furthermore, the opening width>half-height width>bottom width, which is beneficial to increase the number of photons injected into the first perovskite layer, which can correspondingly increase the amount of light absorption, and can better improve the short-circuit current density. In addition, it is also beneficial to better improve the photoelectric conversion efficiency.
[0048] Based on any suitable embodiment of the present application, in some further embodiments, at least a portion of the convex ridges have a bottom width greater than a top width;
[0049] Optionally, based on the proportion of the projected area of the ridges along the longitudinal direction, at least 50% of the ridges have a bottom width that is greater than the top width; further optionally, at least 80% of the ridges have a bottom width that is greater than the top width.
[0050] Optionally, based on the proportion of the projected area of the ridges along the longitudinal direction, at least a portion of the ridges have a bottom width > half-height width > top width; further optionally, at least 50% of the ridges have a bottom width > half-height width > top width; further optionally, at least 80% of the ridges have a bottom width > half-height width > top width.
[0051] When the ridge as a whole has a cross-sectional shape of "narrow at the top and wide at the bottom", the bottom width of the ridge is greater than the top width. Furthermore, the bottom width>half-height width>top width, which is beneficial to increase the number of photons incident into the second perovskite layer, and can correspondingly increase the amount of light absorption, which can better improve the short-circuit current density. In addition, it is also beneficial to better improve the photoelectric conversion efficiency.
[0052] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0053] At least a portion of the concave grooves have corners in their extending directions;
[0054] At least a portion of the concave grooves have a non-linear extension direction;
[0055] At least a portion of the concave grooves have intersection nodes;
[0056] At least a portion of the ridges have corners in their extension direction;
[0057] At least a portion of the ridges extending in a direction in which at least a portion of the ridges extend is non-linear;
[0058] At least a portion of the convex edges have intersection nodes;
[0059] The maximum width of at least a portion of the concave grooves within the extended length deviates by no more than 30% from the average width of the concave grooves;
[0060] The maximum width of at least a portion of the ridges within the extended length deviates by no more than 30% from the average width of the ridges;
[0061] The extension length of at least a portion of the concave grooves is greater than or equal to 50 μm;
[0062] The extension length of at least a portion of the ridges is greater than or equal to 50 μm;
[0063] The aspect ratio of at least a portion of the concave grooves is greater than or equal to 2. Optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 5.
[0064] The aspect ratio of at least a portion of the concave grooves is 1 to 10, and can be 5 to 10;
[0065] The aspect ratio of at least a portion of the ridges is greater than or equal to 2. Optionally, the aspect ratio of at least a portion of the ridges is greater than or equal to 5.
[0066] The aspect ratio of at least a portion of the ridges is 1-20, and can be optionally 10-20.
[0067] When at least a portion of the concave grooves have one or more of the following characteristics in the extension direction: (1) there is a corner in the extension direction of the concave groove; (2) at least a section of the length in the extension direction of the concave groove is non-linear; and (3) there are intersection nodes in the concave grooves, in this case, the concave grooves are more likely to be randomly distributed on the non-smooth surface of the first perovskite layer, which is beneficial to shorten the transmission distance of the photons in the concave grooves that contact the first interface twice in a row, which is beneficial to improve the transmission efficiency of the photons, thereby helping to better improve the short-circuit current density and photoelectric conversion efficiency. Among them, the existence of intersection nodes in different concave grooves means that the extension directions of these concave grooves are not parallel or not completely parallel, so that different concave grooves are connected.
[0068] When at least a portion of the ridges have one or more of the following characteristics in the extension direction: (1) there is a corner in the extension direction of the ridges; (2) at least a section of the extension direction of the ridges is non-linear; and (3) there are intersection nodes in the ridges, in this case, the ridges are more likely to be randomly distributed on the non-smooth surface of the first perovskite layer, which is beneficial to shorten the transmission distance of photons contacting the first interface twice at the ridge interface, which is beneficial to improve the transmission efficiency of photons, thereby helping to better improve the optical short-circuit current density and electrical conversion efficiency. Among them, the existence of intersection nodes in different ridges means that the extension directions of these ridges are not parallel or not completely parallel, so that different ridges are connected.
[0069] When the concave grooves and the convex ridges respectively satisfy at least one of the above-mentioned characteristics, it is beneficial to more effectively exert the synergistic effect between the concave grooves and the convex ridges, while increasing the number of photons and the amount of light absorption in the first perovskite layer and the second perovskite layer, which can better improve the short-circuit current density. In addition, it is also beneficial to better improve the photoelectric conversion efficiency.
[0070] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0071] The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° in an extension length region of at least 30 μm;
[0072] The angle between the extension directions of at least a portion of two adjacent convex ridges satisfies ≤30° in an extension length region of at least 30 μm.
[0073] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0074] The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 30 μm; optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 50 μm; further optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 80 μm;
[0075] The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° over an extension length of at least 50 μm; optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° over an extension length of at least 80 μm;
[0076] The angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 30 μm; optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 50 μm; further optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 80 μm;
[0077] The angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤30° over an extension length of at least 50 μm; optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤30° over an extension length of at least 80 μm.
[0078] The regularity of the concave grooves in the non-smooth surface of the first perovskite layer can be adjusted by adjusting the angle between the extension directions of two adjacent concave grooves. The smaller the angle, the more consistent the extension directions of the two adjacent concave grooves are, and the better the parallelism. The longer the extension length at which the angle of the extension direction is at a relatively small angle, the higher the regularity of the concave grooves, and the better the parallelism between the two adjacent concave grooves.
[0079] The regularity of the ridges in the non-smooth surface of the first perovskite layer can be adjusted by adjusting the angle between the extension directions of two adjacent ridges. The smaller the angle, the more consistent the extension directions of the two adjacent ridges, and the better the parallelism. The longer the extension length at which the angle of the extension direction is relatively small, the higher the regularity of the ridges, and the better the parallelism between the two adjacent ridges.
[0080] When the concave groove and the convex ridge respectively satisfy at least one of the above characteristics, the functions of the concave groove and the convex ridge can be effectively exerted.
[0081] Based on any suitable embodiment of the present application, in some further embodiments, the band gap of the first perovskite layer is greater than the band gap of the second perovskite layer;
[0082] Optionally, the band gap of the first perovskite layer is 1.2 eV to 2.4 eV, and optionally 1.6 eV to 2.3 eV; the band gap of the second perovskite layer is 1.0 eV to 1.4 eV.
[0083] By regulating the band gap of the perovskite layer, the wavelength range in which the perovskite layer can absorb photons can be regulated. When the band gaps of the first perovskite layer and the second perovskite layer are respectively controlled within the above ranges, it is beneficial to better broaden the absorbable wavelength band of the incident light. Combined with the special morphology of the first interface, the first perovskite layer and the second perovskite layer can have a higher total light absorption and light utilization rate as a whole, which can better improve the photoelectric conversion efficiency and short-circuit current density.
[0084] Based on any suitable embodiment of the present application, in some further embodiments, the first perovskite layer includes a first perovskite metal halide, and the halogen in the first perovskite metal halide includes bromine and iodine; optionally, the halogen in the first perovskite metal halide is a combination of bromine and iodine;
[0085] Optionally, the second perovskite layer includes a second perovskite-type metal halide, and the halogen in the second perovskite-type metal halide includes iodine; further optionally, the halogen in the second perovskite-type metal halide is iodine.
[0086] According to the composition design of the perovskite metal halide in the first perovskite layer, bromine and iodine elements can be set in the perovskite precursor solution at the same time. By adjusting the atomic molar ratio of the two elements, the size-related parameters of the grooves and ridges (such as length, width, depth or height, aspect ratio or height-to-width ratio, half-height width, half-height cross-section and the average value of any of the above parameters, etc.), distribution-related parameters (average spacing, proportion of the projected area of the grooves or ridges on the non-smooth surface, the ratio of the average half-height width of the ridges to the average half-height width of the grooves, the ratio of the sum of the areas of the half-height cross-sections of the ridges to the sum of the areas of the half-height cross-sections of the grooves) and other parameters can be controlled, thereby flexibly adjusting the enhancement effect of the concave-convex interface on the short-circuit current density and photoelectric conversion efficiency.
[0087] In addition, by adjusting the halogen composition of the perovskite-type metal halide in the first perovskite layer and the second perovskite layer, it is also possible to adjust the band gap difference in the two light-absorbing layers and the first interface morphology, thereby broadening the absorbable band of incident light, promoting more photons to be incident into the perovskite layer in the stacked solar cell through the first interface, and improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.
[0088] Based on any suitable embodiment of the present application, in some further embodiments, the atomic molar ratio of bromine element to iodine element in the first perovskite metal halide is (3 - y):y, where 0 < y ≤ 2; optionally, 1 ≤ y ≤ 2.
[0089] According to the composition design of the perovskite metal halide in the first perovskite layer, the atomic molar ratio of bromine element to iodine element in the perovskite precursor solution can be adjusted, thereby regulating the comprehensive performance of the short - circuit current density and photoelectric conversion efficiency of the tandem solar cell. By adjusting the atomic molar ratio of bromine element to iodine element in the perovskite metal halide in the first perovskite layer within the above range, the short - circuit current density of the tandem solar cell can be preferably improved, and it can also be used to improve the photoelectric conversion efficiency.
[0090] Based on any suitable embodiment of the present application, in some further embodiments, at least a part of the perovskite grains in the first perovskite layer are through - type grains, and both ends of the through - type grains along the longitudinal direction are respectively located on both side surfaces of the first perovskite layer.
[0091] When the perovskite grains in the first perovskite layer include through - type grains along the thickness direction of the first perovskite layer (i.e., along the longitudinal direction), it means that these perovskite grains grow continuously in the longitudinal direction, with fewer cracks in the longitudinal cross - section of the first perovskite layer, presenting large - sized grains that penetrate longitudinally. At this time, the through - type grains that penetrate the first perovskite layer longitudinally are conducive to making the carriers transport more smoothly and efficiently, reducing the non - radiative recombination caused by grain boundaries, and improving the short - circuit current density and photoelectric conversion efficiency of the device.
[0092] Based on any suitable embodiment of the present application, in some further embodiments, the lateral size of at least a part of the through - type grains is greater than or equal to 400 nm; where the lateral direction is orthogonal to the longitudinal direction, and the lateral size of the through - type grains represents the maximum size among the grain sizes in the lateral cross - section.
[0093] Optionally, the lateral size of at least a part of the through - type grains is greater than or equal to 400 nm, and can be optionally greater than or equal to 500 nm.
[0094] Optionally, the average lateral size of the through - type grains is 300 nm - 2 μm, can be optionally 400 nm - 1 μm, and further optionally 500 nm - 800 nm.
[0095] By controlling the lateral size of the through - type grains, the number of interfaces between perovskite grains can be adjusted. The larger the lateral size, the fewer the number of through - seams between grains, and correspondingly, the fewer defects and higher quality of the perovskite layer. By controlling the lateral size of the through - type grains within the above range, it is beneficial to fully exert the promoting effect of the aforementioned through - type grains.
[0096] Based on any suitable embodiment of the present application, in some further embodiments, in at least a portion of the width region of the longitudinal cross section of the first perovskite layer, the area percentage of the through-type grains relative to the longitudinal cross section is greater than or equal to 80%, and may be greater than or equal to 90%;
[0097] Optionally, at least a portion of the width region of the longitudinal cross section of the first perovskite layer corresponds to a width region of at least 10 μm.
[0098] By controlling the area percentage of the through-type grains in the longitudinal section of the first perovskite layer, the effect of the through-type grains can be adjusted. When the area percentage of the through-type grains relative to the longitudinal section of the first perovskite layer is controlled within the above range, it is beneficial to give full play to the advantages of the through-type grains and to improve the carrier transmission and photoelectric conversion efficiency.
[0099] Based on any suitable embodiment in the present application, in some further embodiments, on the longitudinal cross-section of the first perovskite layer, the area percentage of the through-type grains with a lateral size greater than or equal to 400 nm relative to the longitudinal cross-section is greater than or equal to 80%, and can be optionally greater than or equal to 90%.
[0100] By controlling the area ratio of the larger through-type grains in the longitudinal section of the first perovskite layer, the role of the through-type grains can be adjusted. When the area ratio of the through-type grains with a certain lateral size relative to the longitudinal section of the first perovskite layer is controlled within the above range, it is beneficial to give full play to the advantages of the through-type grains and to improve the carrier transmission and photoelectric conversion efficiency.
[0101] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features:
[0102] The first carrier transport layer and the third carrier transport layer are both electron transport layers, and the second carrier transport layer and the fourth carrier transport layer are both hole transport layers, or the first carrier transport layer and the third carrier transport layer are both hole transport layers, and the second carrier transport layer and the fourth carrier transport layer are both electron transport layers;
[0103] The stacked solar cell further comprises a first electrode and a second electrode, wherein the first electrode is located on a side of the first perovskite subcell away from the carrier recombination layer, and the second electrode is located on a side of the second perovskite subcell away from the carrier recombination layer; the first electrode is a transparent electrode;
[0104] At least one side of the first carrier transport layer includes a heterogeneous carrier blocking layer;
[0105] At least one side of the second carrier transport layer includes a heterogeneous carrier blocking layer;
[0106] At least one side of the third carrier transport layer comprises a heterogeneous carrier blocking layer;
[0107] At least one side of the fourth carrier transport layer includes a foreign carrier blocking layer.
[0108] The first perovskite sub-cell and the second perovskite sub-cell may both be nip-type or both be pin-type.
[0109] When the first electrode is a transparent electrode, the incident light entering the stacked solar cell can be incident from the first electrode side. At this time, when the incident light is first emitted from the first perovskite layer side to the first interface, the first interface is conducive to achieving the aforementioned effect of improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.
[0110] In addition, a heterogeneous carrier blocking layer may be provided on at least one side of one or more of the first carrier transport layer, the second carrier transport layer, the third carrier transport layer and the fourth carrier transport layer to block the transport of heterogeneous carriers, thereby facilitating the reduction of the recombination probability of electrons and holes.
[0111] Based on any suitable embodiment in the present application, in some further embodiments, the first perovskite sub-cell and the second perovskite sub-cell form an integrated structure with two ends.
[0112] Based on any suitable implementation in the present application, in some further implementations, the stacked solar cell is a two-end stacked solar cell.
[0113] Based on any suitable embodiment in the present application, in some further embodiments, the tandem solar cell is an all-perovskite tandem solar cell.
[0114] In a second aspect of the present application, a method for preparing the perovskite-based tandem solar cell according to the first aspect of the present application is provided, comprising the following steps: sequentially stacking a first carrier transport layer, a first perovskite layer, a second carrier transport layer, a carrier recombination layer, a third carrier transport layer, a second perovskite layer, a fourth carrier transport layer and a second electrode on a surface of one side of a first electrode to prepare the perovskite-based tandem solar cell;
[0115] The method of stacking the first perovskite layer on the side of the first carrier transport layer facing away from the first electrode comprises the following steps:
[0116] Applying the precursor solution I of the first perovskite layer to the surface of the first carrier transport layer on the side away from the first electrode to form a coating layer I;
[0117] The coating layer I is subjected to vacuum flash evaporation treatment and annealing treatment to form the first perovskite layer, and the non-smooth surface is formed on a side of the first perovskite layer away from the first electrode.
[0118] By preparing the first perovskite layer through the vacuum flash evaporation process, the aforementioned concave grooves and convex ridges can be formed on the surface of the first perovskite layer close to the carrier recombination layer, increasing the amount of photons in contact with the perovskite layer and the light utilization rate, improving the short-circuit current density of the stacked solar cell, and improving the photoelectric conversion efficiency. In addition, it can also promote the formation of large-sized through-type grains, promote carrier transmission and photoelectric conversion efficiency.
[0119] Based on any suitable embodiment of the present application, in some further embodiments, the preparation method satisfies one or more of the following characteristics:
[0120] The vacuum flash evaporation treatment is carried out under negative pressure conditions, and the negative pressure condition is less than or equal to 100 Pa, and can be selected from 50 Pa to 100 Pa;
[0121] The temperature for the vacuum flash treatment is -10°C to 100°C, optionally 0°C to 30°C, and further optionally 20°C to 30°C;
[0122] The duration of the vacuum flash treatment is 10s to 100s, optionally 10s to 30s, and further optionally 15s to 25s;
[0123] The annealing treatment is performed by a hot stage, optionally, a 30°C to 200°C hot stage, further optionally, a 90°C to 110°C hot stage, and further optionally, a 98°C to 102°C hot stage;
[0124] The annealing time of the annealing treatment is 30s to 60min, optionally 5min to 20min, and further optionally 14min to 16min.
[0125] Based on any suitable embodiment of the present application, in some further embodiments, the step of coating the precursor solution I of the first perovskite layer onto the surface of the first carrier transport layer on the side away from the first electrode comprises:
[0126] Spin coating a portion of the precursor solution I onto a surface of the first carrier transport layer that is away from the first electrode at a first rotation speed;
[0127] Accelerating the rotation speed from the first rotation speed to a second rotation speed, and continuing to spin-coat another portion of the precursor liquid I at the second rotation speed;
[0128] Wherein, the second rotation speed is greater than the first rotation speed.
[0129] Based on any suitable embodiment of the present application, in some further embodiments, the preparation method satisfies one or more of the following characteristics:
[0130] The first rotation speed is 1000 rpm to 6000 rpm, and can be optionally 1000 rpm to 2000 rpm; the spin coating is performed at the first rotation speed for 8 s to 12 s;
[0131] In the step of accelerating the rotation speed from the first rotation speed to the second rotation speed, the acceleration is 200 rpm / s to 2000 rpm / s, and can be optionally 800 rpm / s to 1200 rpm / s;
[0132] The second rotation speed is 3000 rpm to 4500 rpm, and can be optionally 3800 rpm to 4200 rpm; the spin coating is performed at the second rotation speed for 18 s to 22 s.
[0133] By adjusting one or more parameters in the preparation process of the first perovskite layer and regulating the surface morphology and / or grain size of the first perovskite layer as needed, the short-circuit current density and the comprehensive performance of the photoelectric conversion efficiency of the stacked solar cell can be better improved through process parameter optimization.
[0134] In a third aspect of the present application, an electrical device is provided, comprising at least one of the perovskite-based tandem solar cells described in the first aspect of the present application and the perovskite-based tandem solar cells prepared by the preparation method described in the second aspect of the present application.
[0135] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0136] In order to better describe and illustrate the embodiments or examples of those applications disclosed herein, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered as limiting the scope of any of the disclosed applications, the embodiments or examples currently described, and the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the accompanying drawings:
[0137] Figure 1 This is an optical microscope observation image of the non-smooth surface of the first perovskite layer in one embodiment of the present application.
[0138] Figure 2 Schematic diagram of the transmission path of incident light at the non-smooth surface of the first perovskite layer in one embodiment of the present application.
[0139] Figure 3 This is an optical microscope observation picture of a stacked solar cell from the glass substrate side in one embodiment of the present application, wherein a transparent electrode is disposed on the surface of the glass substrate close to the carrier recombination layer.
[0140] Figure 4 This is a scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell prepared by a vacuum flash evaporation method in one embodiment of the present application.
[0141] Figure 5 This is a scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell prepared by a vacuum flash evaporation method in one embodiment of the present application.
[0142] Figure 6 This is a scanning electron microscope (SEM) image of a transverse cross section of a wide bandgap perovskite layer prepared by vacuum flash evaporation in one embodiment of the present application.
[0143] Figure 7 This is a schematic diagram of the transmission path of the incident light at the interface between the wide bandgap perovskite layer and the intermediate interconnect layer in a comparative example of the present application. The wide bandgap perovskite layer is prepared by the anti-solvent method in this comparative example.
[0144] Figure 8 This is an optical microscope observation picture of the all-perovskite stacked solar cell from the glass substrate side in a comparison of the present application, wherein a transparent electrode is arranged on the surface of the glass substrate close to the carrier recombination layer.
[0145] Fig. 9 This is a scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell prepared by an anti-solvent method in a comparative example of the present application.
[0146] Fig.10 Schematic diagram of a stacked solar cell in one embodiment of the present application; it includes a first perovskite sub-cell, a carrier recombination layer, and a second perovskite sub-cell stacked in sequence.
[0147] Fig.11Schematic diagram of a stacked solar cell in one embodiment of the present application; the stacked solar cell includes a substrate layer, a first perovskite sub-cell, a carrier recombination layer, and a second perovskite sub-cell stacked in sequence; wherein the first perovskite sub-cell includes a first electrode, a first carrier transport layer, a first perovskite layer, and a second carrier transport layer stacked in sequence, and the second perovskite sub-cell includes a third carrier transport layer, a second perovskite layer, a fourth carrier transport layer, and a second electrode stacked in sequence; wherein the first electrode, the first carrier transport layer, the first perovskite layer, the second carrier transport layer, the carrier recombination layer, the third carrier transport layer, the second perovskite layer, the fourth carrier transport layer, and the second electrode are stacked in sequence.
[0148] Fig.12 Schematic diagram of a stacked solar cell in one embodiment of the present application; the stacked solar cell includes a substrate layer, a first perovskite sub-cell, a carrier recombination layer and a second perovskite sub-cell stacked in sequence; wherein the first perovskite sub-cell includes a first electrode, a first carrier transport layer, a first perovskite layer and a second carrier transport layer stacked in sequence, and the second perovskite sub-cell includes a third carrier transport layer, a second perovskite layer, a fourth carrier transport layer and a second electrode stacked in sequence; wherein the first electrode, the first carrier transport layer, the first perovskite layer, the second carrier transport layer, the carrier recombination layer, the third carrier transport layer, the second perovskite layer, the fourth carrier transport layer and the second electrode are stacked in sequence; wherein the fourth carrier transport layer and the second carrier transport layer are both electron transport layers, and the third carrier transport layer and the first carrier transport layer are both hole transport layers; the side of the fourth carrier transport layer close to the second perovskite layer includes a second hole blocking layer, and the side of the second carrier transport layer close to the first perovskite layer includes a first hole blocking layer.
[0149] Fig.13 This is a schematic diagram of an electrical device in which a stacked solar cell according to one embodiment of the present application is used as a power generation device.
[0150] Explanation of the accompanying drawings: 10 is a stacked solar cell; 100 is a substrate layer; 200 is a first perovskite sub-cell; 220 is a first electrode; 230 is a first carrier transport layer; 240 is a first perovskite layer; 250 is a second carrier transport layer; 2501 is a first hole blocking layer; 400 is an intermediate interconnect layer; 410 is a carrier recombination layer; 600 is a second perovskite sub-cell; 630 is a third carrier transport layer; 640 is a second perovskite layer; 650 is a fourth carrier transport layer; 6501 is a second hole blocking layer; 660 is a second electrode; 6 is an electrical device; the double-headed arrow X indicates the thickness direction of the first perovskite layer; 900 is an intermediate interconnect layer with smooth interfaces on both sides, and 920 and 940 are two perovskite layers on both sides of the intermediate interconnect layer, respectively.
[0151] Figure 4 , Figure 5 , Figure 6 and Fig. 9 In the table, EHT corresponds to the accelerating voltage, WD corresponds to the working distance, Mag corresponds to the magnification, Signal A corresponds to the detector model, Date corresponds to the test date, and Iprobe corresponds to the probe current. DETAILED DESCRIPTION
[0152] Hereinafter, some embodiments of the laminated solar cell, preparation method and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0153] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are also listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer greater than or equal to 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0154] In this application, "multiple", "multiple", "multiple", "multiple times", "several" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two. It is understood that when "any number" of items are involved, it refers to any suitable combination of multiple items, that is, the combination of "any number" of items is performed in a manner that does not conflict and can implement this application.
[0155] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0156] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0157] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, and can preferably be performed sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0158] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" or "A is selected from the group consisting of a1, a2 and a3", and the feature or solution of "A includes not only a1, a2 and a3, but also other members".
[0159] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0160] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "optional" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent. Unless otherwise specified, the descriptions of "optionally include", "optionally contain", etc. in this application, taking "optionally include" as an example, mean "may include or not include". As a non-limiting example, "optional substance A" means including or not including substance A.
[0161] In the present application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a group consisting of A, B, and "a combination of A and B". Among them, "comprising A and / or B" can mean "comprising A, comprising B, and comprising A and B", and can also mean "comprising A, comprising B, or comprising A and B", which can be properly understood according to the sentence in which it is located.
[0162] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.
[0163] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the technical solution that can implement the present application.
[0164] Herein, "preferred", "better", "more preferred", "suitable", "better", and "preferable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.
[0165] In the present application, “further”, “furthermore”, “particularly”, “for example”, “such as”, “example”, “for example”, etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of the present application.
[0166] In the present application, the terms "first", "second", "third", "fourth", etc. in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0167] In the present application, the term "room temperature" generally refers to 4°C to 35°C, and may refer to 20°C±5°C. In some embodiments of the present application, room temperature refers to 20°C to 30°C.
[0168] In this application, when the unit of a data range is mentioned, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3~5h or 3-5h both mean that the units of the left endpoint "3" and the right endpoint "5" are both h (hours), which has the same meaning as 3h~5h. This is applicable not only to time units, but also to unit descriptions of parameters such as temperature, size, and band gap.
[0169] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Furthermore, the weight described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0170] In the present application, "greater than or equal to" can be equivalently expressed as "≥", "less than or equal to" can be equivalently expressed as "≤", "greater than" can be equivalently expressed as ">", and "less than" can be equivalently expressed as "<". In the present application, if there is no other explanation, "greater than or equal to" can be regarded as providing two solutions of "greater than" and "equal to". In the present application, if there is no other explanation, "less than or equal to" can be regarded as providing two solutions of "less than" and "equal to".
[0171] In the present application, exemplary descriptions such as "in some implementation modes (or examples)" and "in one implementation mode (or example)" may include but are not limited to the following meanings: these solutions may be combined with other solutions in a suitable manner to form new technical solutions.
[0172] In response to the above-mentioned common technical problems, on the first aspect, the present application provides a perovskite-based tandem solar cell, which includes a perovskite light-absorbing layer, can provide a higher short-circuit current density, and is also beneficial to improving the photoelectric conversion efficiency.
[0173] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence; the surface of the first perovskite layer close to the carrier recombination layer is a non-smooth surface, and the non-smooth surface is provided with a concave groove; further, at least a portion of the concave grooves have different widths at at least a portion of the depth positions. Optionally, the aspect ratio of the concave groove is greater than 1. Optionally, the band gap of the first perovskite layer in the first perovskite subcell is different from the band gap of the second perovskite layer in the second perovskite subcell.
[0174] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence; the surface of the first perovskite layer close to the carrier recombination layer is a non-smooth surface, and the non-smooth surface is provided with concave grooves; further, convex ridges are formed between at least a portion of adjacent concave grooves. Optionally, the aspect ratio of the concave grooves is greater than 1. Optionally, the band gap of the first perovskite layer in the first perovskite subcell is different from the band gap of the second perovskite layer in the second perovskite subcell.
[0175] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence; the surface of the first perovskite layer close to the carrier recombination layer is a non-smooth surface, and the non-smooth surface is provided with convex ridges; further, a concave groove is formed between at least a portion of adjacent convex ridges. Optionally, the aspect ratio of the concave groove is greater than 1. Optionally, the band gap of the first perovskite layer in the first perovskite subcell is different from the band gap of the second perovskite layer in the second perovskite subcell.
[0176] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence; the surface of the first perovskite layer near the carrier recombination layer is a non-smooth surface, and the non-smooth surface is provided with ridges; further, at least a portion of the ridges have different widths at at least a portion of the height positions. Optionally, the band gap of the first perovskite layer in the first perovskite subcell is different from the band gap of the second perovskite layer in the second perovskite subcell.
[0177] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence; the surface of the first perovskite layer on one side close to the carrier recombination layer is a non-smooth surface, the non-smooth surface is provided with concave grooves, and convex ridges are formed between at least a portion of adjacent concave grooves; the tandem solar cell satisfies at least one of the following features (i) and (ii): (i) at least a portion of the concave grooves have different widths at at least a portion of the depth position; and, (ii) at least a portion of the convex ridges have different widths at at least a portion of the height position. Optionally, the aspect ratio of the concave grooves is greater than 1. Optionally, the band gap of the first perovskite layer in the first perovskite subcell is different from the band gap of the second perovskite layer in the second perovskite subcell.
[0178] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence; the surface of one side of the first perovskite layer close to the carrier recombination layer is a non-smooth surface, the non-smooth surface is provided with concave grooves, and convex ridges are formed between at least a portion of adjacent concave grooves; the concave-convex interface formed by the concave grooves and the convex ridges and the adjacent structural layer is recorded as the first interface; the tandem solar cell satisfies at least one of the following features (i) and (ii): (i) at least a portion of the concave grooves have different widths at at least a portion of the depth position; and, (ii) at least a portion of the convex ridges have different widths at at least a portion of the height position. The tandem solar cell has good comprehensive performance of short-circuit current density and photoelectric conversion efficiency. Optionally, the band gap of the first perovskite layer in the first perovskite subcell is different from the band gap of the second perovskite layer in the second perovskite subcell.
[0179] In some embodiments, a perovskite-based tandem solar cell is provided, the tandem solar cell comprising a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell stacked in sequence, the first perovskite subcell comprising a first perovskite layer, the second perovskite subcell comprising a second perovskite layer; the band gap of the first perovskite layer is different from the band gap of the second perovskite layer;
[0180] Wherein, the thickness direction of the first perovskite layer is recorded as the longitudinal direction;
[0181] The surface of the first perovskite layer on one side close to the carrier recombination layer is a non-smooth surface, and the non-smooth surface is provided with concave grooves; convex ridges are formed between at least a portion of adjacent concave grooves; and the concave-convex interface formed by the concave grooves, the convex ridges and the adjacent structural layer is recorded as a first interface;
[0182] The stacked solar cell meets at least one of the following characteristics:
[0183] At least a portion of the concave grooves have different widths at at least a portion of the depth positions;
[0184] At least some of the ridges have different widths at at least some of their heights.
[0185] In this application, unless otherwise specified, "tandem solar cell based on perovskite" refers to a tandem solar cell in which the light absorption layer in at least one sub-cell includes a perovskite semiconductor material. Unless otherwise specified, "tandem solar cell" has a well-known meaning in the art, and refers to a solar cell obtained by stacking sub-cells based on semiconductor materials with different band gaps, which can broaden the absorption spectrum of the solar cell and reduce thermal relaxation losses.
[0186] In the present application, unless otherwise specified, "perovskite layer" refers to a light-absorbing layer containing a perovskite semiconductor material, which can be divided into different perovskite layers according to the different sub-cells in which they are located, such as the first perovskite layer contained in the first perovskite sub-cell, the second perovskite layer contained in the second perovskite sub-cell, etc.
[0187] In the present application, unless otherwise specified, a "carrier recombination layer" is a structural layer for recombination of electrons and holes transmitted from the first perovskite sub-cell and the second perovskite sub-cell, or a structural layer for recombination of holes and electrons transmitted from the first perovskite sub-cell and the second perovskite sub-cell, so that the first perovskite sub-cell and the second perovskite sub-cell are connected in series.
[0188] In this application, unless otherwise specified, "band gap" has a well-known meaning in the art and can be analyzed, compared and confirmed by conventional methods in the art. Without limitation, the band gap of a material can be determined by its absorption spectrum or emission spectrum, and commonly used optical methods include ultraviolet-visible absorption spectrum, photoluminescence spectrum and Raman spectrum.
[0189] In some embodiments, the band gap of the first perovskite layer is greater than the band gap of the second perovskite layer. In this case, the first perovskite layer is also referred to as a wide band gap perovskite layer, and the second perovskite layer is also referred to as a narrow band gap perovskite layer. In this application, unless otherwise specified, "wide band gap" and "narrow band gap" are relative concepts, and the absolute value of the band gap is not particularly limited, indicating that the band gap of the "wide band gap structural layer" is greater than the band gap of the "narrow band gap structural layer".
[0190] In this application, unless otherwise specified, the thickness direction of the first perovskite layer is referred to as “longitudinal direction”. Figure 10-12The X direction is marked in the figure. Along the longitudinal direction, the first perovskite layer has two surfaces that are opposite to each other, where the surface close to the carrier recombination layer can be recorded as the first surface, and the surface away from the carrier recombination layer can be recorded as the second surface. The section direction of the thickness of the first perovskite layer refers to the direction orthogonal to the longitudinal direction, which can also be recorded as the transverse direction. When the first perovskite layer is a thin film with uniform thickness, the longitudinal direction and the transverse direction are orthogonal, and the first surface and the second surface are parallel. Fig.10 For example, Fig.10 Schematic diagram of a stacked solar cell 10 in one embodiment of the present application; it includes a first perovskite sub-cell 200, a carrier recombination layer 410 and a second perovskite sub-cell 600 stacked in sequence.
[0191] In the present application, unless otherwise specified, the direction from the first perovskite layer to the second perovskite layer in the longitudinal direction is referred to as a “first direction”.
[0192] In the present application, unless otherwise specified, a “concave groove” refers to a strip-shaped groove with an aspect ratio greater than 1.
[0193] In the present application, unless otherwise specified, the "non-smooth surface" in the first perovskite layer refers to the presence of a non-smooth area on the surface of one side of the first perovskite layer close to the carrier recombination layer (i.e., the first surface), and the first surface in the non-smooth area has ups and downs along the thickness direction of the first perovskite layer, so that the non-smooth surface has a certain degree of roughness.
[0194] In the application, unless otherwise specified, the "concave groove" on the non-smooth surface of the first perovskite layer refers to a depression with a certain depth along the thickness direction of the first perovskite layer, the concave groove has a certain aspect ratio in the horizontal direction, and the projection along the longitudinal direction forms a long strip profile, and the length direction of the long strip profile can be recorded as the extension direction of the concave groove. Unless otherwise specified, the aspect ratio of the concave groove is greater than 1.
[0195] In the application, unless otherwise specified, the "convex ridge" on the non-smooth surface of the first perovskite layer refers to a protrusion with a certain height along the thickness direction of the first perovskite layer, the convex ridge has a certain aspect ratio in the horizontal direction, and the projection along the longitudinal direction forms a long strip profile, and the length direction of the long strip profile can be recorded as the extension direction of the convex ridge. Unless otherwise specified, the aspect ratio of the convex ridge is greater than 1.
[0196] Convex ridges are formed between adjacent concave grooves, and concave grooves are formed between adjacent convex ridges. The patterns formed by multiple groups of staggered concave grooves and convex ridges can be called "wrinkle patterns".
[0197] It can be understood that due to the presence of the concave grooves, there are non-smooth areas in the non-smooth surface.
[0198] By providing perovskite light-absorbing layers with different band gaps in the stacked solar cell, photons of different wavelengths can be fully absorbed, thermal relaxation losses can be reduced, and the utilization rate of incident light can be improved. A non-smooth surface including concave grooves and convex ridges can be provided on the surface of one side of the first perovskite layer close to the carrier recombination layer, so that the non-smooth surface and the adjacent surface of the adjacent structural layer form a long strip-shaped concave-convex interface, which can be recorded as the first interface. When at least one of the two characteristics of "at least a portion of the concave grooves have different widths at at least a portion of the depth position" and "at least a portion of the convex ridges have different widths at at least a portion of the height position" is met, at least a portion of the photons incident on the first interface can experience at least one of multiple refractions and multiple reflections at the first interface. For photons directed toward the first interface, compared with the situation in which a traditional smooth interface is only reflected and / or refracted once after contacting the interface, the non-smooth first interface in the present application can increase the contact opportunity between the photons and the first interface, increase the probability of the photons being captured by the perovskite layer in the perovskite-based tandem solar cell, and increase the efficiency of light utilization; for photons that are not absorbed by the first perovskite layer and are directed toward the first interface, the probability of the photons entering the second perovskite layer can be increased, thereby increasing the number of photons in the absorbable band of the second perovskite layer; for photons that are still not absorbed by the second perovskite layer and are directed toward the first interface, the probability of entering the first perovskite layer can be increased, thereby increasing the number of photons in the absorbable band of the first perovskite layer. Therefore, the overall current level of the tandem solar cell can be improved, the short-circuit current density can be improved, and in addition, it is also beneficial to improve the photoelectric conversion efficiency.
[0199] “The extension direction of the concave groove” refers to the extension direction of the concave groove in the lateral direction. In the lateral direction, the extension direction of the concave groove can be obtained by collecting the peripheral extension contour of the concave groove on the first surface of the first perovskite layer, connecting the width centers of the extension contour at different length positions in sequence, and the obtained contour width center connection line can be used to characterize the extension direction of the concave groove, and the contour width center connection line can be recorded as the “extension line of the concave groove”. In the extension contour of the concave groove located on the first surface, the length of the contour width center connection line of the concave groove can be recorded as the “length of the concave groove”.
[0200] On a non-smooth surface with concave grooves, the "average spacing of the concave grooves" can be obtained by statistically analyzing the average distance between the extension lines. For example, multiple positions can be collected to obtain the average distance between the extension lines at different collection positions of the concave grooves. The average spacing of the concave grooves in the selected area can also be estimated by the following formula: A1 / L1, where A1 is the projected area of the selected non-smooth area along the longitudinal direction, and L1 is the sum of the lengths of the extension lines of the concave grooves in the selected non-smooth area.
[0201] The "longitudinal section of the concave groove" is a section that is orthogonal to the extension line of the concave groove and parallel to the thickness direction of the first perovskite layer. The contour line of the longitudinal section is an open line that is open at the top and concave downward, wherein the position close to the outside of the first perovskite layer in the longitudinal section contour line is recorded as "above". The two upper end points of the longitudinal section contour line are connected and recorded as the "opening connection line" of the concave groove. The length of the opening connection line is recorded as the "opening width of the concave groove" or "the width of the concave groove". The position of the longitudinal contour line farthest from the opening connection line is recorded as the "bottom of the concave groove". A straight line parallel to the opening connection line is drawn at the bottom position. The length of the line segment of the straight line between the longitudinal section contour lines is recorded as the "bottom width of the concave groove". The vertical distance between each point on the longitudinal section contour line and the opening line corresponds to the depth of the concave groove at different contour positions, and the maximum vertical distance is recorded as the "depth of the concave groove"; a straight line parallel to the opening line is drawn at the midpoint of the maximum depth (that is, the half-height), and the length of the line segment of the straight line between the longitudinal section contour lines is recorded as the "half-height width of the concave groove", and the corresponding mean can be recorded as the "half-height width of the concave groove".
[0202] The ratio of the length of the concave groove to the width of the concave groove is recorded as the “aspect ratio of the concave groove”. Unless otherwise specified, the aspect ratio of the concave groove is >1.
[0203] The ratio of the depth of the concave groove to the width of the concave groove is recorded as the "aspect ratio of the concave groove".
[0204] Cross section at half height of the concave groove The area surrounded by the concave groove contour line on the cross section orthogonal to the longitudinal direction at half height of the concave groove is recorded as the “concave groove half height cross section”.
[0205] The average width, average depth, average half-height width and average length of the concave groove can be obtained by performing arithmetic averaging on multi-point test values of the corresponding parameters.
[0206] "Extension direction of the ridge" refers to the extension direction of the ridge in the horizontal direction. In the horizontal direction, the extension direction of the ridge can be obtained by projecting the ridge along the longitudinal direction onto the longitudinal orthogonal plane, collecting the outer projection contour of the ridge as the extension contour, connecting the width centers of the extension contour at different length positions in sequence, and the obtained contour width center connection line can be used to characterize the extension direction of the ridge, and the contour width center connection line can be recorded as the "extension line of the ridge". In the extension contour of the ridge located on the first surface, the length of the contour width center connection line of the ridge can be recorded as the "length of the ridge".
[0207] On a non-smooth surface with ridges, the "average spacing of ridges" can be obtained by statistically analyzing the average distance between each extension line, for example, by collecting multiple positions and averaging the distance between each extension line at different collection positions of the ridges. The average spacing of ridges in the selected area can also be estimated by the following formula: A1 / L2, where A1 is the projected area of the selected non-smooth area along the longitudinal direction, and L2 is the sum of the lengths of the extension lines of each ridge in the selected non-smooth area.
[0208] The "longitudinal section of the ridge" is a section that is orthogonal to the extension line of the ridge and parallel to the thickness direction of the first perovskite layer. The contour line of the longitudinal section is an open line that is open at the bottom and bulges toward the top, wherein the position of the outer side of the first perovskite layer of the raw material in the longitudinal section contour line is recorded as the "bottom". The two bottom endpoints of the longitudinal section contour line are connected and recorded as the "opening connection line" of the ridge. The length of the opening connection line is recorded as the "bottom width of the ridge" or "width of the ridge". The position of the longitudinal contour line farthest from the opening connection line is recorded as the "top of the ridge". A straight line parallel to the ridge opening connection line is drawn at the top position. The length of the line segment of the straight line between the longitudinal section contour lines is recorded as the "top width of the ridge". The vertical distance between each point on the longitudinal section contour line and the opening line corresponds to the height of the different contour positions of the ridge, and the maximum vertical distance is recorded as the "height of the ridge"; a straight line parallel to the opening line is drawn at the midpoint of the maximum depth (that is, half the height), and the length of the line segment of this straight line between the longitudinal section contour lines is recorded as the "half-height width of the ridge", and the corresponding mean can be recorded as the "half-height width of the ridge".
[0209] The ratio of the length of the rib to the width of the rib is recorded as the "aspect ratio of the rib". Unless otherwise specified, the aspect ratio of the rib is >1.
[0210] The ratio of the height of the ridge to the width of the ridge is recorded as the "ridge aspect ratio".
[0211] When the concave grooves and the convex ridges are arranged alternately, adjacent concave grooves and the convex ridges share side surfaces, and the average spacing of the convex ridges is substantially consistent with the average spacing of the concave grooves. In addition, the depth of the concave grooves is substantially consistent with the height of the convex ridges in terms of mean value.
[0212] Cross section at half-height of ridge The area enclosed by the ridge outline on a cross section perpendicular to the longitudinal direction at half-height of the ridge is recorded as "cross section at half-height of ridge".
[0213] The average width, average depth, average length, average half-height width and average aspect ratio of the ridges can be obtained by performing arithmetic averaging on multi-point test values of the corresponding parameters.
[0214] In the present application, the shape parameters of the concave grooves and convex ridges on the non-smooth surface of the first perovskite layer can be tested and analyzed by methods including but not limited to the following:
[0215] (1) obtaining a topographic image or surface roughness curve of the non-smooth surface of the first perovskite layer by scanning electron microscopy (SEM), optical microscope photographs, step profilers, etc., and analyzing the following information and / or parameters by combining with image analysis software such as Image-J: including but not limited to the extension profile of the concave grooves on the non-smooth surface of the first perovskite layer, the extension line of the concave grooves, the extension direction of the concave grooves, the length of the concave grooves, the average interval of the concave grooves, the extension profile of the ridges on the non-smooth surface of the first perovskite layer, the extension line of the ridges, the extension direction of the ridges, the length of the ridges, the average interval of the ridges, the projection area of the non-smooth area along the longitudinal direction, etc.;
[0216] (2) obtaining a longitudinal cross-sectional view of the first perovskite layer by scanning electron microscopy (SEM), optical microscope photographs, etc., and combining with image analysis software such as Image-J to test and analyze the following information and / or parameters: longitudinal cross-section of the concave groove, contour line of the longitudinal cross-section of the concave groove, opening line of the concave groove, opening width of the concave groove, width of the concave groove, bottom width of the concave groove, depth of the concave groove, half-height width of the concave groove, aspect ratio of the concave groove, depth-to-width ratio of the concave groove, half-height cross-section of the concave groove, longitudinal cross-section of the convex ridge, contour line of the longitudinal cross-section of the convex ridge, opening line of the convex ridge, bottom width of the convex ridge, width of the convex ridge, top width of the convex ridge, height of the convex ridge, half-height width of the convex ridge, aspect ratio of the convex ridge, aspect ratio of the convex ridge, half-height cross-section of the convex ridge, etc.;
[0217] (3) Parameter average values: average width of concave grooves, average half-height width of concave grooves, average depth of concave grooves, average depth-to-width ratio of concave grooves, average length of concave grooves, average length-to-width ratio of concave grooves, average half-height cross-section of concave grooves, average width of convex ridges, average half-height width of convex ridges, average height of convex ridges, average height-to-width ratio of convex ridges, average length of convex ridges, average length-to-width ratio of convex ridges, average half-height cross-section of convex ridges, etc. average values can be obtained by collecting corresponding parameter values at multiple positions and performing simple arithmetic average calculations. The number of collection positions can be appropriately selected according to the level of differentiation of the shapes and sizes of the concave grooves and convex ridges. For example, the minimum amount of data collection can be determined by controlling the standard deviation of the average value to be less than or equal to (≤) 10% of the average value. As a non-limiting example, the width values of the concave grooves at an appropriate number of positions (such as 20) can be collected, and the average value obtained by performing simple arithmetic average calculations can be used as the "average width of the concave grooves".
[0218] The method in the following embodiment can be used to obtain a sample to be tested containing a first perovskite layer. Taking SEM observation as an example, a component in which the first perovskite layer has been deposited on the first carrier transport layer and the second carrier transport layer has not yet been deposited can be selected as a sample to be tested, and the test analysis can be performed in both the longitudinal and transverse directions: (1) the observation surface is the transverse surface of the exposed side of the first perovskite layer; (2) a glass knife is used to cut the component or stacked solar cell containing the first perovskite layer longitudinally, and the longitudinal section is upwardly subjected to SEM testing; (3) a cryo-focused electron beam (FIB) is used to slice along the longitudinal direction, and the obtained section is a longitudinal section, and the cross section is subjected to SEM morphology observation.
[0219] It can be understood that some parameter values in the present application based on the statistical results of a larger sample set can be determined by random sampling statistics. For example, some parameter values of the concave grooves in the entire non-smooth surface area (average width, average half-height width, average depth, average aspect ratio, average length, etc.), some parameter values of the ridges (average width, average half-height width, average height, average aspect ratio, average length, etc.) and other parameters can be determined by the statistical average values among multiple randomly selected areas within the non-smooth surface.
[0220] Based on any suitable embodiment in the present application, in some further embodiments, the average half-height width of the ridges is 1 μm to 2.5 μm, and can be optionally 1.5 μm to 2 μm.
[0221] In this application, unless otherwise specified, "surface roughness" refers to the surface unevenness formed by the staggered arrangement of micro-nano-scale convexities and concave portions on the surface. The smaller the surface roughness, the smoother the surface; the larger the surface roughness, the more uneven the surface. In the non-smooth surface of the first perovskite layer, the larger the surface roughness caused by the concave grooves and convex ridges, the more uneven the non-smooth surface is.
[0222] In this application, unless otherwise specified, the "surface roughness" of a non-smooth surface can be characterized by the distance between the highest point and the lowest point of the surface in the longitudinal direction. Generally, the concave portion between the two nearest protrusions with a height difference between the highest point and the lowest point greater than or equal to 100nm (≥100nm) is recorded as a "concave groove", and fluctuations less than 100nm are regarded as morphological changes within the concave groove. Unless otherwise specified, the "surface roughness" of a specified area is numerically equal to the average depth of the concave grooves in the specified area, or is numerically equal to the average height of the ridges in the specified area.
[0223] The surface roughness test method of the selected non-smooth area can be a step profiler test, but is not limited thereto. The step profiler can be a probe type profilometer. The test method of the following embodiment can be referred to, and the size of the concave groove and / or convex ridge can be statistically analyzed according to the surface roughness curve obtained by the test.
[0224] In some embodiments, the surface roughness is measured using a step profiler method.
[0225] The shape and size of the concave groove (such as length, width, depth, aspect ratio, length-to-depth ratio, depth-to-width ratio, etc.), the distribution amount and distribution mode of the concave groove on the non-smooth surface of the first perovskite layer, the shape and size of the ridge (such as length, width, height, aspect ratio, length-to-height ratio, height-to-width ratio, etc.), the distribution amount and distribution mode of the ridge on the non-smooth surface of the first perovskite layer, etc., can affect the surface roughness of the non-smooth surface. By controlling the surface roughness of the non-smooth area in the non-smooth surface within a more appropriate range, the non-smooth surface can be controlled to have a more appropriate morphology, which is conducive to giving full play to the light capture effect of the first interface, and is more conducive to improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.
[0226] For photons emitted from the first perovskite layer or the second perovskite layer to the first interface, generally speaking, a portion of the photons enter the adjacent structural layer after one refraction, and a portion of the photons are reflected once and emitted back to the first perovskite layer. At this time, the concave-convex morphology at the first interface can be used to allow at least a portion of the photons to undergo at least one of the following effects: (i) multiple reflections and refractions are used to allow at least a portion of the photons to refract out of the first perovskite layer at the ridge interface. At this time, at least a portion of the photons that can be absorbed by the second perovskite layer (which can be recorded as second-band photons) can be captured by the second perovskite layer after a second or more reflections. (ii) utilizing the effects of secondary refraction and reflection, at least a portion of the photons can be refracted into the first perovskite layer after being reflected at the concave groove interface. At this time, at least a portion of the photons that can be absorbed by the first perovskite layer (which can be recorded as first-band photons) can be captured and absorbed by the first perovskite layer after secondary refraction; based on the above-mentioned effects of the concave-convex morphology at the first interface, the contact opportunity between the perovskite light-absorbing layer and the photons in the stacked solar cell can be increased, the utilization rate of the incident light by the stacked solar cell can be improved, the short-circuit current density of the stacked solar cell can be improved, and in addition, it is also beneficial to improve the photoelectric conversion efficiency of the stacked solar cell.
[0227] In this application, photons that can be absorbed by the first perovskite layer are referred to as “first wavelength band photons”.
[0228] The concave-convex interface morphology of the first perovskite layer near the carrier recombination layer can be obtained by preparing the first perovskite layer by a vacuum flash evaporation process, and can also be adjusted by adjusting the vacuum flash evaporation process parameters and the composition of the perovskite material of the first perovskite layer. In some embodiments, increasing the bromine content of the perovskite material in the first perovskite layer is conducive to promoting the formation of wrinkle lines, and is conducive to increasing the depth-to-width ratio and wrinkle density of the concave grooves. During the vacuum flash evaporation process, the higher the vacuum degree, the faster the pumping speed of the solvent removal, the greater the depth-to-width ratio of the concave grooves, the greater the wrinkle density formed, the smaller the spacing between the concave grooves, and the smaller the spacing between the convex ridges. In some embodiments, lowering the temperature of the sample during the vacuum flash evaporation process is also conducive to promoting the formation of wrinkle lines, and is conducive to increasing the depth-to-width ratio and wrinkle density of the concave grooves; taking the process parameters of 100Pa vacuum flash evaporation for 20s as an example, in one embodiment, the average depth-to-width ratio of the concave grooves in the wrinkle lines is 0.3, and the average spacing between the concave grooves is 15μm.
[0229] In some embodiments, the ratio of the sum of the extended lengths of the concave grooves to the sum of the extended lengths of the convex ridges is 0.9 to 1.1, and may further be 1.
[0230] Based on any suitable embodiment in the present application, in some further embodiments, the morphologies of the interfaces formed by different structural layers between the first perovskite layer and the second perovskite layer are substantially matched.
[0231] When the morphologies of the interfaces between the structural layers between the first perovskite layer and the second perovskite layer are basically consistent, each structural layer has a uniform thickness; when the morphologies of the interfaces formed by different structural layers between the first perovskite layer and the second perovskite layer are basically matched, the different structural layers have a uniform thickness, and at this time, a non-smooth surface with a similar morphology can be formed on the surface of the second perovskite layer close to the first perovskite layer; corresponding to the "convex-concave" interface on the surface of the first perovskite layer, a corresponding "convex-concave" interface (which can be recorded as a second interface) can be formed on the surface of the second perovskite layer, and the second interface is also beneficial to increase the number of absorbable wavelength photons in the perovskite layer in the stacked solar cell and the light utilization rate, which is beneficial to improving the overall current level of the stacked solar cell and the photoelectric conversion efficiency.
[0232] The light band that can be absorbed by the second perovskite layer is recorded as the "second band", and the interface formed by the second perovskite layer near the middle interconnection layer and the adjacent structural layer is recorded as the "second interface". When the light of the second band passes through the first perovskite layer, part of the light will be reflected by the interface at the second interface. Due to the presence of the concave-convex wrinkle lines, the reflected light will reach the second interface again and be absorbed by the second perovskite layer, thereby increasing the effect of the second perovskite layer on the light absorption of the second band.
[0233] Figure 2 FIG. 1 is a schematic diagram of the transmission path of incident light at the non-smooth surface of the first perovskite layer in one embodiment of the present application. For a conventional smooth interface, the transmission path of incident light can be referred to Figure 7 .
[0234] Figure 2 Schematic diagram of the transmission path of incident light at the non-smooth surface of the first perovskite layer in one embodiment of the present application. In this embodiment, a vacuum flash evaporation process is used to prepare the first perovskite layer. Figure 2 The structure shown includes a first perovskite layer 240, an intermediate interconnect layer 400 and a second perovskite layer 640 stacked in sequence. Figure 2 The structure shown is as follows: on the basis of forming the first perovskite layer, an intermediate interconnection layer with uniform thickness is deposited by evaporation, and then a second perovskite layer is prepared. At this time, a wrinkled intermediate interconnection layer with basically matching concave-convex morphology and uniform thickness is formed at the interface between the two perovskite sub-cells. When the photons of the second band pass through the first perovskite layer, part of the light will be reflected by the interface at the second interface, or part of the reflected light from the second electrode may be reflected at the second interface or the first interface. Due to the presence of the concave-convex wrinkle lines between the first perovskite layer and the second perovskite layer, the reflected light can reach the second interface again and be absorbed by the second perovskite layer, thereby increasing the effect of the second perovskite layer on the absorption of light in the second band. In some further embodiments, the first perovskite layer is a wide band gap, and the second perovskite layer is a narrow band gap.
[0235] Figure 7 This is a schematic diagram of the transmission path of the incident light at the interface between the intermediate interconnect layer 900 with smooth interfaces on both sides and the perovskite layer 920 and the perovskite layer 940 on both sides in a comparison of the present application. The first perovskite layer is prepared by the anti-solvent method. In this comparison, the interface between the two perovskite sub-cells is a flat and smooth planar structure. Some long-wave incident light passes through the first perovskite and then passes through the intermediate interconnect layer into the second perovskite and is absorbed, but part of the light will be reflected once at the interface, resulting in light loss. In some further embodiments, the first perovskite layer is a wide bandgap and the second perovskite layer is a narrow bandgap.
[0236] The morphology of the first surface in the first perovskite layer and the morphology of the intermediate interconnection layer between the first perovskite layer and the second perovskite layer can be observed, photographed, and analyzed from the transparent electrode side using an optical microscope, with a magnification of, for example, 200X. For example, when the first electrode is a transparent electrode, part of the visible light passes through the first perovskite layer, and part of it is reflected and passes through the transparent electrode side, making it possible to observe with an optical microscope. The longitudinal and transverse cross-sectional morphologies can also be observed using focused ion beam (LIB) slicing combined with scanning electron microscopy (SEM) technology.
[0237] Figure 3This is an optical microscope observation image of a laminated solar cell from the glass substrate side in one embodiment of the present application, wherein a transparent electrode is provided on the surface of the glass substrate near the carrier recombination layer, and obvious wrinkles can be observed. In this example, after the first perovskite layer is prepared by vacuum flash evaporation, an optical microscope observation image from the first perovskite layer side is shown as follows: Figure 2 As shown, an obvious wrinkled surface morphology can be observed, the concave grooves and convex ridges are generally evenly staggered, the width of the concave grooves does not vary much, and the width of the convex ridges is relatively stable. Figure 3 and Figure 2 The observation results are quite consistent.
[0238] Figure 8 This is an optical microscope observation picture of the all-perovskite stacked solar cell from the glass substrate side in a comparison of the present application, wherein a transparent electrode is provided on the surface of the glass substrate close to the carrier recombination layer, and no obvious wrinkles are observed.
[0239] Based on any suitable embodiment of the present application, in some further embodiments, an intermediate interconnection layer is provided between the first perovskite layer and the second perovskite layer; from the first perovskite layer to the second perovskite layer, the intermediate interconnection layer sequentially includes a second carrier transport layer, the carrier recombination layer and a fourth carrier transport layer, wherein one of the second carrier transport layer and the fourth carrier transport layer is an electron transport layer, and the other is a hole transport layer;
[0240] The internal structural layers and the interfaces on both sides of the intermediate interconnection layer have substantially matching concave-convex morphologies.
[0241] When the internal structural layers and the interfaces on both sides of the intermediate interconnection layer have basically matching concave-convex morphologies, the structural layers in the intermediate interconnection layer have uniform thicknesses and the interfaces are basically parallel. At this time, on the one hand, it is beneficial to give full play to the reflection and refraction effects of the concave grooves and convex ridges at the interfaces on both sides, which is beneficial to increase the number of absorbable band photons and light utilization rate in the perovskite layer in the stacked solar cell, which is beneficial to improve the overall current level of the stacked solar cell, and also beneficial to improve the photoelectric conversion efficiency.
[0242] Based on any suitable embodiment in the present application, in some further embodiments, the width of at least a portion of the ridges is 0.5 μm to 4 μm, optionally 1 μm to 4 μm, and further optionally 2 μm to 3.5 μm. The width of at least a portion of the ridges can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc.
[0243] Based on any suitable embodiment in the present application, in some further embodiments, the half-height width of at least a portion of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm. The half-height width of at least a portion of the ridges can also be selected from any of the following values, or from an interval consisting of any two of the following values: 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.5 μm, etc.
[0244] Based on any suitable embodiment in the present application, in some further embodiments, the height of at least a portion of the ridges is ≥100nm, which can be 100nm-500nm, and further can be 100nm-250nm. The height of the ridges can also be selected from any of the following values, or from an interval consisting of any two of the following values: 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 180nm, 200nm, 210nm, 220nm, 240nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc.
[0245] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average width of the ridge is 0.5 μm to 4 μm, optionally 1 μm to 4 μm, and further optionally 2 μm to 3.5 μm. In at least a portion of the non-smooth surface, the average width of the ridge can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc.
[0246] Based on any suitable embodiment of the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average half-height width of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm. In at least a portion of the non-smooth surface, the average half-height width of the ridges can also be selected from any of the following values, or from an interval consisting of any two of the following values: 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.5 μm, etc.
[0247] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average height of the ridges is 100nm to 500nm, and can be 100nm to 250nm. In at least a portion of the non-smooth surface, the average height of the ridges can also be selected from any of the following values, or from an interval consisting of any two of the following values: 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 180nm, 200nm, 210nm, 220nm, 240nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc.
[0248] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0249] The aspect ratio of at least a portion of the ridges is greater than 1, optionally, the aspect ratio of at least a portion of the ridges is ≥ 2, further optionally, the aspect ratio of at least a portion of the ridges is ≥ 3, and further optionally, the aspect ratio of at least a portion of the ridges is ≥ 5;
[0250] The width of at least a portion of the ridges is 0.5 μm to 4 μm, optionally 1 μm to 4 μm, and further optionally 2 μm to 3.5 μm;
[0251] The half-height width of at least a portion of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm;
[0252] The height of at least a portion of the ridges is ≥100 nm, and may be 100 nm to 500 nm, and may be further 100 nm to 250 nm;
[0253] In at least a portion of the non-smooth surface, the average width of the ridges is 0.5 μm to 4 μm, optionally 1 μm to 4 μm, and further optionally 2 μm to 3.5 μm;
[0254] In at least a portion of the non-smooth surface, the average half-height width of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm;
[0255] In at least a portion of the non-smooth surface, the average height of the ridges is 100 nm to 500 nm, and may be 100 nm to 250 nm;
[0256] Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is ≥ 0.1 mm 2, further optional to ≥0.5mm 2 , further optional to ≥0.6mm 2 .
[0257] In the present application, unless otherwise specified, the aforementioned “at least a portion of the ridges” may be measured in terms of the extended length of the ridges, and may mean at least 80% of the extended length, or 90% to 100% of the extended length.
[0258] In this application, unless otherwise specified, the "at least a portion of the area in the non-smooth surface" refers to the non-smooth surface portion corresponding to the projection area area whose projection area along the longitudinal direction is at least a certain value. "At least a portion of the area in the non-smooth surface" can also be expressed as "the non-smooth surface area corresponding to at least a portion of the projection area of the non-smooth surface along the longitudinal direction". The projection area of at least a portion of the non-smooth surface along the longitudinal direction can be selected to be ≥0.1mm 2 , further optional to ≥0.5mm 2 , further optional to ≥0.6mm 2 , non-limiting example such as 960000μm 2 .
[0259] The aspect ratio, width, half-height width, height of the ridges and the average values of these parameters may be combined in any appropriate manner.
[0260] By adjusting one or more parameters of the width, half-width, height of the ridges and the average values of these parameters, the probability of photons emitted from the inside of the first perovskite layer to the first interface after being reflected multiple times at the ridge interface of the first perovskite layer can be adjusted. By controlling the above one or more parameters within the above range, more photons are absorbed by the second perovskite layer, which is conducive to enhancing the utilization rate of photons that are not absorbed after passing through the first perovskite layer. These photons may include photons in the absorbable band of the second perovskite layer, so the short-circuit current density can be better improved, and it is also more conducive to improving the photoelectric conversion efficiency of the stacked solar cell. The photons emitted from the side of the first perovskite layer to the first interface can come from external incident light.
[0261] Based on any suitable embodiment in the present application, in some further embodiments, the width of at least a portion of the concave grooves is ≤1.2μm, and can be 0.5μm to 1μm. The width of at least a portion of the concave grooves can also be selected from any of the following values, or less than or equal to any of the following values, or selected from the interval consisting of any two of the following values: 0.5μm, 0.6μm, 0.8μm, 1μm, 1.1μm, 1.2μm, etc.
[0262] Based on any suitable embodiment in the present application, in some further embodiments, the average half-height width of the concave groove is ≤1 μm, which can be selected from 0.2 μm to 0.7 μm, and further selected from 0.3 μm to 0.55 μm. The average half-height width of the concave groove can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.9 μm, etc.
[0263] Based on any suitable embodiment in the present application, in some further embodiments, the depth of at least a portion of the concave grooves is ≥ 100nm, and can be 100nm to 500nm, and can be further 100nm to 250nm. The depth of at least a portion of the concave grooves can also be selected from any of the following values, or from an interval consisting of any two of the following values: 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 180nm, 200nm, 210nm, 220nm, 240nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, etc.
[0264] Based on any suitable embodiment in the present application, in some further embodiments, the aspect ratio of at least a portion of the concave grooves is 0.03-0.5, optionally 0.2-0.5, and further optionally 0.25-0.35. The aspect ratio of at least a portion of the concave grooves can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.03, 0.05, 0.1, 0.15, 0.2, 0.22, 0.24, 0.25, 0.26, 0.275, 0.28, 0.30, 0.32, 0.35, 0.36, 0.38, 0.40, 0.42, 0.45, 0.46, 0.48, 0.50, etc.
[0265] In the present application, unless otherwise specified, “at least a portion of the concave groove” may be measured by the extended length of the concave groove, and may mean at least 80% of the extended length, or 90% to 100% of the extended length.
[0266] Based on any suitable embodiment of the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average width of the concave groove is 0.3μm to 1μm, and can be 0.5μm to 1μm. The average width of the concave groove can also be selected from any of the following values, or less than or equal to any of the following values from 0.4μm to 1μm, or selected from the interval consisting of any two of the following values: 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, etc.
[0267] Based on any suitable embodiment of the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.2μm to 0.7μm, and can be 0.3μm to 0.55μm. In at least a portion of the non-smooth surface, the average half-height width of the concave groove can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, etc.
[0268] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average depth of the concave groove is 100nm to 500nm, and can be 100nm to 250nm. The average depth of the concave groove can be selected from any of the following values, or from an interval consisting of any two of the following values: 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 180nm, 200nm, 210nm, 220nm, 240nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc.
[0269] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average depth-to-width ratio of the concave groove is 0.03-0.5, optionally 0.2-0.5, and further optionally 0.25-0.35. The average depth-to-width ratio of the concave groove can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.03, 0.05, 0.1, 0.15, 0.2, 0.22, 0.24, 0.25, 0.26, 0.275, 0.28, 0.30, 0.32, 0.35, 0.36, 0.38, 0.40, 0.42, 0.45, 0.46, 0.48, 0.50, etc.
[0270] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0271] The aspect ratio of at least a portion of the concave grooves is greater than 1, optionally, the aspect ratio of at least a portion of the concave grooves is ≥3, further optionally, the aspect ratio of at least a portion of the concave grooves is ≥5, further optionally, the aspect ratio of at least a portion of the concave grooves is ≥10, and more optionally, the aspect ratio of at least a portion of the concave grooves is ≥15;
[0272] The width of at least a portion of the concave grooves is ≤1.2 μm, and may be 0.5 μm to 1 μm;
[0273] The half-height width of at least a portion of the concave grooves is ≤1 μm, and can be optionally 0.2 μm to 0.7 μm;
[0274] The depth of at least a portion of the concave grooves is ≥100 nm, and may be 100 nm to 500 nm, and may be further 100 nm to 250 nm;
[0275] The aspect ratio of at least a portion of the concave grooves is 0.03 to 0.5, optionally 0.2 to 0.5, and further optionally 0.25 to 0.35;
[0276] In at least a portion of the non-smooth surface, the average width of the concave groove is 0.3 μm to 1 μm, and can be 0.5 μm to 1 μm;
[0277] In at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.2 μm to 0.7 μm, and can be 0.3 μm to 0.55 μm;
[0278] In at least a portion of the non-smooth surface, the average depth of the concave groove is 100nm to 500nm, and can be 100nm to 250nm;
[0279] In at least a portion of the non-smooth surface, the average depth-to-width ratio of the concave groove is 0.03 to 0.5, optionally 0.2 to 0.5, and further optionally 0.25 to 0.35;
[0280] Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is ≥ 0.1 mm 2 , further optional to ≥0.5mm 2 , further optional to ≥0.6mm 2 .
[0281] The aspect ratio, width, half-height width, depth, aspect ratio of the concave groove and the average values of these parameters may be combined in any appropriate manner.
[0282] By adjusting one or more parameters of the concave groove width, half-height width, depth, aspect ratio and the average value of these parameters, the probability of photons emitted from the second perovskite layer side to the first interface entering the first perovskite layer at the concave groove interface of the first perovskite layer can be adjusted. By controlling the above one or more parameters within the above range, the optical path of the photons that are not absorbed after the interface reflection of the second perovskite layer is significantly increased in the first perovskite layer, and more photons can be absorbed by the first perovskite layer. This part of the photons may include photons in the absorbable band of the first perovskite layer, so that the light utilization rate can be improved, thereby better improving the overall current level and improving the photoelectric conversion efficiency of the stacked solar cell. Among them, the photons emitted from the second perovskite layer side to the first interface can come from the reflected light at the second electrode.
[0283] By comprehensively adjusting the width and length of the concave groove, the proportion of the longitudinal projection area of the concave groove in the longitudinal projection area of the first perovskite layer can be adjusted. The higher the proportion, the more significant the comprehensive improvement effect of the concave groove on the overall current level and photoelectric conversion efficiency. The longitudinal projection area of the first perovskite layer can be regarded as being substantially equal to the longitudinal projection area of the non-smooth surface. Therefore, the proportion of the longitudinal projection area of the concave groove in the longitudinal projection area of the first perovskite layer is substantially equal to the percentage of the sum of the longitudinal projection areas of the concave groove relative to the longitudinal projection area of the non-smooth surface.
[0284] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average spacing of the ridges is 1 μm to 20 μm, and can be 10 μm to 20 μm. In at least a portion of the non-smooth surface, the average spacing of the ridges can also be selected from any of the following values, or from an interval consisting of any two of the following values: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.
[0285] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average spacing of the concave grooves is 1 μm to 20 μm, and can be 10 μm to 20 μm. In at least a portion of the non-smooth surface, the average spacing of the concave grooves can also be selected from any of the following values, or from an interval consisting of any two of the following values: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.
[0286] Based on any suitable embodiment in the present application, in some further embodiments, the half-height width of at least a portion of the convex ridges is greater than the half-height width of adjacent concave grooves.
[0287] Based on any suitable embodiment of the present application, in some further embodiments, in at least a portion of the non-smooth surface, the ratio of the average half-width of the ridge to the average half-width of the concave groove is 1 to 6, and can be further selected as 4 to 5. The ratio of the average half-width of the ridge to the average half-width of the concave groove can also be selected from any of the following values, or from an interval consisting of any two of the following values: 1.0, 1.5, 1.6, 2, 2.5, 3, 3.5, 3.6, 4, 4.5, 5, 5.5, 6, etc.
[0288] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the ratio of the sum of the half-height cross-section areas of the ridges to the sum of the half-height cross-section areas of the concave grooves is 1 to 36, and can further be 10 to 30. In at least a portion of the non-smooth surface, the ratio of the sum of the half-height cross-section areas of the ridges to the sum of the half-height cross-section areas of the concave grooves can be selected from any of the following values, or from an interval consisting of any two of the following values: 1, 1.1, 1.2, 1.21, 1.25, 1.3, 1.4, 1.44, 1.5, 1.56, 1.6, 1.69, 1.7, 1.8, 1.9, 1.96, 2, 2.25, 2.5, 2.56, 2.6, 2.8, 2.89, 3, 3.2, 3.24, 3.5, 3.6, 2.61, 4, 4.2, 4.4, 4.5, 4.6, 4.8, 4.84, 4.9, 5, 5.2, 5.4, 5.5, 5.6, 5.8 , 6, 6.2, 6.25, 6.4, 6.5, 6.76, 7, 7.2, 7.5, 7.6, 7.8, 7.84, 8, 8.1, 8.2, 8.4, 8.5, 9, 9.5, 9.6, 10, 10.24, 11, 11.56, 12, 12.25, 12.5, 12.6, 12.96, 13, 13. 5, 14, 14.44, 14.5, 16, 16.5, 17, 17.5, 18, 18.48, 19, 19.36, 20, 20.25, 21.26, 22, 23.04, 24, 25, 26, 28, 29.16, 30, 30.25, 31.36, 32, 33.64, 34, 35, 36, etc.
[0289] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the percentage of the sum of the projection areas of the concave grooves along the longitudinal direction relative to the projection area of the non-smooth surface along the longitudinal direction is 5% to 95%, optionally 5% to 90%, further optionally 5% to 70%, and further optionally 5% to 50%. In at least a portion of the non-smooth surface, the percentage of the sum of the projection areas of the concave grooves along the longitudinal direction to the projection area of the non-smooth surface along the longitudinal direction can also be selected from any two of the following percentages or an interval consisting of any two percentages: 5%, 6%, 6.4%, 6.5%, 7%, 8%, 9%, 10%, 12%, 15%, 16%, 18%, 20%, 25%, 30%, 35%, 36%, 38%, 40%, 45%, 48%, 50%, 54%, 55%, 56%, 60%, 64%, 65%, 66%, 68%, 70%, 75%, 80%, 81%, 84%, 85%, 90%, 95%, etc. In at least a portion of the non-smooth surface, the percentage of the sum of the projection areas of the concave grooves along the longitudinal direction to the projection area of the non-smooth surface along the longitudinal direction can also be selected from any of the following ranges: 10% to 95%, 10% to 90%, 10% to 70%, 10% to 50%, 15% to 95%, 15% to 90%, 15% to 70%, 15% to 50%, 20% to 95%, 20% to 90%, 20% to 70%, 20% to 50%, etc.
[0290] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0291] In at least a part of the non-smooth surface, the average spacing of the ridges is 1 μm to 20 μm, and can be 10 μm to 20 μm;
[0292] In at least a portion of the non-smooth surface, the average spacing of the concave grooves is 1 μm to 20 μm, and can be 10 μm to 20 μm;
[0293] The half-height width of at least a portion of the convex ridges is greater than the half-height width of the adjacent concave grooves;
[0294] In at least a portion of the non-smooth surface, the ratio of the average half-height width of the convex ridges to the average half-height width of the concave grooves is 1 to 6, and can further be 4 to 5;
[0295] In at least a portion of the non-smooth surface, the ratio of the sum of the half-height cross-section areas of the ridges to the sum of the half-height cross-section areas of the concave grooves is 1 to 36, and may further be 10 to 30;
[0296] In at least a portion of the non-smooth surface, the sum of the projection areas of the concave grooves along the longitudinal direction relative to the projection area of the non-smooth surface along the longitudinal direction accounts for 5% to 95%, optionally 5% to 90%, and further optionally 5% to 70%;
[0297] Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is ≥ 0.1 mm 2 , further optional to ≥0.5mm 2 , further optional to ≥0.6mm 2 .
[0298] “The percentage of the sum of the projected areas of the concave grooves along the longitudinal direction to the projected area of the non-smooth surface along the longitudinal direction” may reflect the proportion of the concave grooves in the non-smooth surface.
[0299] By adjusting one or more parameters of the average spacing of the ridges, the average spacing of the concave grooves, the ratio of the average half-height width of the ridges to the average half-height width of the concave grooves, and the ratio of the sum of the areas of the half-height cross-sections of the ridges to the sum of the areas of the half-height cross-sections of the concave grooves, the density of the concave grooves and / or the ridges on the non-smooth surface of the first perovskite layer can be adjusted, and the unevenness of the non-smooth surface can be adjusted, thereby adjusting the degree of improvement of the photoelectric conversion effect. By controlling one or more of these parameters within the above range, the concave-convex morphology of the first interface can be fully utilized to make the first perovskite layer and / or the second perovskite layer absorb more photons, which is more conducive to improving the short-circuit current density. In addition, it can also be more conducive to improving the photoelectric conversion efficiency. When external incident light is incident from the first electrode, by controlling the half-height width of at least a portion of the ridges to be greater than the half-height width of the adjacent concave grooves, it is conducive to more photons that are not used by the first perovskite layer in the photons that are initially incident on the first interface Enter the second perovskite layer.
[0300] Based on any suitable embodiment in the present application, in some further embodiments, the opening width of at least a portion of the concave grooves is greater than the bottom width.
[0301] Based on any suitable embodiment in the present application, in some further embodiments, based on the proportion of the projection area of the concave groove along the longitudinal direction, at least 50% of the opening width of the concave groove is greater than the bottom width, and further optionally, at least 80% of the opening width of the concave groove is greater than the bottom width. The percentage of the sum of the projection areas of the concave grooves along the longitudinal direction that meet the "opening width is greater than the bottom width" relative to the sum of the projection areas of all concave grooves on the non-smooth surface can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any of the following percentages and 100%, or selected from the interval consisting of any two of the following percentages: 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc. In some embodiments, 100% of the opening width of the concave grooves is greater than the bottom width. The determination of the above percentage values can be determined by random sampling statistics.
[0302] Based on any suitable embodiment in the present application, in some further embodiments, based on the proportion of the projection area of the concave groove along the longitudinal direction, the opening width of at least a part of the concave grooves> half-height width> bottom width; further optionally, at least 50% of the concave grooves have an opening width> half-height width> bottom width, and further optionally, at least 80% of the concave grooves have an opening width> half-height width> bottom width. The percentage of the sum of the projection areas of the concave grooves along the longitudinal direction that meet the "opening width of the concave groove> half-height width> bottom width" relative to the sum of the projection areas of all concave grooves along the longitudinal direction can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any of the following percentages and 100%, or selected from the interval consisting of any two of the following percentages: 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc. In some embodiments, 100% of the concave grooves have an opening width> half-height width> bottom width. The above percentage values can be determined by random sampling statistics.
[0303] When the concave groove as a whole has a cross-sectional shape of "wide at the top and narrow at the bottom", at this time, the opening width of the concave groove is greater than the bottom width. Furthermore, the opening width>half-height width>bottom width, which is beneficial to increase the number of photons injected into the first perovskite layer, which can correspondingly increase the amount of light absorption, and can better improve the short-circuit current density. In addition, it is also beneficial to better improve the photoelectric conversion efficiency.
[0304] Based on any suitable embodiment in the present application, in some further embodiments, the bottom width of at least a portion of the ridges is greater than the top width.
[0305] Based on any suitable embodiment in the present application, in some further embodiments, based on the proportion of the projection area of the ridge along the longitudinal direction, at least 50% of the ridges have a bottom width greater than the top width, and further optionally, at least 80% of the ridges have a bottom width greater than the top width. The percentage of the sum of the projection areas of the ridges along the longitudinal direction that meet the "bottom width greater than top width" relative to the sum of the projection areas of all ridges on the non-smooth surface can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any of the following percentages and 100%, or selected from the interval consisting of any two of the following percentages: 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc. In some embodiments, 100% of the opening widths of the concave grooves are greater than the bottom width. The above percentage values can be determined by random sampling statistics.
[0306] Based on any suitable embodiment in the present application, in some further embodiments, in terms of the proportion of the projection area of the ridge along the longitudinal direction, at least a portion of the ridges have a bottom width > half-height width > top width; further optionally, at least 50% of the ridges have a bottom width > half-height width > top width, and further optionally, at least 80% of the ridges have a bottom width > half-height width > top width. The percentage of the sum of the projection areas of the ridges along the longitudinal direction that meet the "bottom width > half-height width > top width" relative to the sum of the projection areas of all ridges on the non-smooth surface can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any of the following percentages and 100%, or selected from the interval consisting of any two of the following percentages: 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc. In some embodiments, 100% of the concave grooves have an opening width > half-height width > bottom width. The above percentage values can be determined by random sampling statistics.
[0307] When the ridge as a whole has a cross-sectional shape of "narrow at the top and wide at the bottom", the bottom width of the ridge is greater than the top width. Furthermore, the bottom width>half-height width>top width, which is beneficial to increase the number of photons incident into the second perovskite layer, and can correspondingly increase the amount of light absorption, which can better improve the short-circuit current density. In addition, it is also beneficial to better improve the photoelectric conversion efficiency.
[0308] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0309] At least a portion of the concave grooves have corners in their extending directions;
[0310] At least a portion of the concave grooves have a non-linear extension direction;
[0311] At least a portion of the concave grooves have intersection nodes;
[0312] At least a portion of the ridges have corners in their extension direction;
[0313] At least a portion of the ridges extending in a direction in which at least a portion of the ridges extend is non-linear;
[0314] At least a portion of the convex edges have intersection nodes;
[0315] The maximum width of at least a portion of the concave grooves within the extended length deviates by no more than 30% from the average width of the concave grooves;
[0316] The maximum width of at least a portion of the ridges within the extended length deviates by no more than 30% from the average width of the ridges;
[0317] The extension length of at least a portion of the concave grooves is ≥50 μm;
[0318] The extension length of at least a portion of the ridges is ≥50 μm;
[0319] The aspect ratio of at least a portion of the concave grooves is ≥2, and optionally, the aspect ratio of at least a portion of the concave grooves is ≥5;
[0320] The aspect ratio of at least a portion of the concave grooves is 1 to 10, and can be 5 to 10;
[0321] The aspect ratio of at least a portion of the ridges is ≥ 2, and optionally, the aspect ratio of at least a portion of the ridges is ≥ 5;
[0322] The aspect ratio of at least a portion of the ridges is 1-20, and can be optionally 10-20.
[0323] Based on any suitable embodiment in the present application, in some further embodiments, the aspect ratio of at least a portion of the concave grooves is greater than 1. Optionally, the aspect ratio of at least a portion of the concave grooves is ≥2. Further optionally, the aspect ratio of at least a portion of the concave grooves is ≥3. Further optionally, the aspect ratio of at least a portion of the concave grooves is ≥5. The aspect ratio of at least a portion of the concave grooves may also be any of the following values, or greater than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 9, 10, etc. The aspect ratio of at least a portion of the concave grooves may also be any of the following ranges: greater than 1 and less than or equal to 10, 2 to 10, 5 to 10, etc. See. Figure 1 .
[0324] Based on any suitable embodiment in the present application, in some further embodiments, the aspect ratio of at least a portion of the ridges is greater than 1, optionally, the aspect ratio of at least a portion of the ridges is ≥3, further optionally, the aspect ratio of at least a portion of the ridges is ≥5, further optionally, the aspect ratio of at least a portion of the ridges is ≥10, and more optionally, the aspect ratio of at least a portion of the ridges is ≥15. The aspect ratio of at least a portion of the ridges may also be any of the following values, or greater than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc. The aspect ratio of at least a portion of the ridges may also be any of the following ranges: greater than 1 and less than or equal to 20, 2 to 20, 5 to 20, 10 to 20, etc. See. Figure 1 .
[0325] When at least a portion of the concave grooves have one or more of the following characteristics in the extension direction: (1) there is a corner in the extension direction of the concave groove; (2) at least a section of the length in the extension direction of the concave groove is non-linear; and (3) there are intersection nodes in the concave grooves, in this case, the concave grooves are more likely to be randomly distributed on the non-smooth surface of the first perovskite layer, which is beneficial to shorten the transmission distance of the photons in the concave grooves that contact the first interface twice in a row, which is beneficial to improve the transmission efficiency of the photons, thereby helping to better improve the short-circuit current density and photoelectric conversion efficiency. Among them, the existence of intersection nodes in different concave grooves means that the extension directions of these concave grooves are not parallel or not completely parallel, so that different concave grooves are connected.
[0326] When at least a portion of the ridges have one or more of the following characteristics in the extension direction: (1) there is a corner in the extension direction of the ridges; (2) at least a section of the extension direction of the ridges is non-linear; and (3) there are intersection nodes in the ridges, in this case, the ridges are more likely to be randomly distributed on the non-smooth surface of the first perovskite layer, which is beneficial to shorten the transmission distance of photons contacting the first interface twice at the ridge interface, which is beneficial to improve the transmission efficiency of photons, thereby helping to better improve the optical short-circuit current density and electrical conversion efficiency. Among them, the existence of intersection nodes in different ridges means that the extension directions of these ridges are not parallel or not completely parallel, so that different ridges are connected.
[0327] When the concave grooves and the convex ridges respectively satisfy at least one of the above-mentioned characteristics, it is beneficial to more effectively exert the synergistic effect between the concave grooves and the convex ridges, while increasing the number of photons and the amount of light absorption in the first perovskite layer and the second perovskite layer, which can better improve the short-circuit current density. In addition, it is also beneficial to better improve the photoelectric conversion efficiency.
[0328] In the application, unless otherwise specified, when statistically analyzing “the deviation of the maximum width of the concave groove within the extended length relative to the average width of the concave groove” and “the deviation of the maximum width of the ridge within the extended length relative to the average width of the ridge”, the 10% length of the sealed end portions at both ends may not be included in the statistical range of the extended length.
[0329] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0330] The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° in an extension length region of at least 30 μm;
[0331] The angle between the extension directions of at least a portion of two adjacent convex ridges satisfies ≤30° in an extension length region of at least 30 μm.
[0332] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0333] The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 30 μm; optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 50 μm; further optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 80 μm;
[0334] The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° over an extension length of at least 50 μm; optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° over an extension length of at least 80 μm;
[0335] The angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 30 μm; optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 50 μm; further optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 80 μm;
[0336] The angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤30° over an extension length of at least 50 μm; optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤30° over an extension length of at least 80 μm.
[0337] Based on any suitable embodiment in the present application, in some further embodiments, one or more of the following features are met (the reference in any of the following features can also be selected from any suitable value or range in the context):
[0338] At least a portion of adjacent concave grooves and convex ridges have the same extension direction over an extension length of at least 50 μm;
[0339] At least a portion of adjacent concave grooves and convex ridges extend in the same direction over at least 60% of their adjacent lengths.
[0340] In the present application, unless otherwise specified, "the extending directions are consistent" means that the angle does not exceed 10°, further may not exceed 5°, and further may not exceed 2°.
[0341] The regularity of the concave grooves in the non-smooth surface of the first perovskite layer can be adjusted by adjusting the angle between the extension directions of two adjacent concave grooves. The smaller the angle, the more consistent the extension directions of the two adjacent concave grooves are, and the better the parallelism. The longer the extension length at which the angle of the extension direction is at a relatively small angle, the higher the regularity of the concave grooves, and the better the parallelism between the two adjacent concave grooves.
[0342] The regularity of the ridges in the non-smooth surface of the first perovskite layer can be adjusted by adjusting the angle between the extension directions of two adjacent ridges. The smaller the angle, the more consistent the extension directions of the two adjacent ridges, and the better the parallelism. The longer the extension length at which the angle of the extension direction is relatively small, the higher the regularity of the ridges, and the better the parallelism between the two adjacent ridges.
[0343] When the concave groove and the convex ridge respectively satisfy at least one of the above characteristics, the functions of the concave groove and the convex ridge can be effectively exerted.
[0344] Based on any suitable embodiment in the present application, in some further embodiments, the band gap of the first perovskite layer is greater than the band gap of the second perovskite layer.
[0345] When the first perovskite layer is a wide-bandgap perovskite layer with a relatively wide bandgap, and the second perovskite layer is a narrow-bandgap perovskite layer with a relatively narrow bandgap, the first electrode can be a transparent electrode, the first perovskite sub-cell can be a top cell, and the second perovskite sub-cell can be a bottom cell. At this time, it is beneficial to more effectively utilize the different bandgap differences of different perovskite layers to make more full use of incident light.
[0346] Based on any suitable embodiment in the present application, in some further embodiments, the band gap of the first perovskite layer is 1.2eV to 2.4eV, and can be optionally 1.6eV to 2.3eV; the band gap of the second perovskite layer is 1.0eV to 1.4eV.
[0347] By regulating the band gap of the perovskite layer, the wavelength range in which the perovskite layer can absorb photons can be regulated. When the band gaps of the first perovskite layer and the second perovskite layer are respectively controlled within the above ranges, it is beneficial to better broaden the absorbable wavelength band of the incident light. Combined with the special morphology of the first interface, the first perovskite layer and the second perovskite layer can have a higher total light absorption and light utilization rate as a whole, which can better improve the photoelectric conversion efficiency and short-circuit current density.
[0348] Based on any suitable embodiment in the present application, in some further embodiments, the first perovskite layer includes a first perovskite-type metal halide, and the halogen in the first perovskite-type metal halide includes bromine and iodine elements; optionally, the halogen in the first perovskite-type metal halide is a combination of bromine and iodine elements.
[0349] According to the composition design of the perovskite metal halide in the first perovskite layer, bromine and iodine elements can be set in the perovskite precursor solution at the same time. By adjusting the atomic molar ratio of the two elements, the size-related parameters of the grooves and ridges (such as length, width, depth or height, aspect ratio or height-to-width ratio, half-height width, half-height cross-section and the average value of any of the above parameters, etc.), distribution-related parameters (average spacing, proportion of the projected area of the grooves or ridges on the non-smooth surface, the ratio of the average half-height width of the ridges to the average half-height width of the grooves, the ratio of the sum of the areas of the half-height cross-sections of the ridges to the sum of the areas of the half-height cross-sections of the grooves) and other parameters can be controlled, thereby flexibly adjusting the enhancement effect of the concave-convex interface on the short-circuit current density and photoelectric conversion efficiency.
[0350] Based on any suitable embodiment in the present application, in some further embodiments, the second perovskite layer includes a second perovskite metal halide, and the halogen in the second perovskite metal halide includes iodine; further optionally, the halogen in the second perovskite metal halide is iodine.
[0351] In addition, by adjusting the halogen composition of the perovskite-type metal halide in the first perovskite layer and the second perovskite layer, it is also possible to adjust the band gap difference in the two light-absorbing layers and the first interface morphology, thereby broadening the absorbable band of incident light, promoting more photons to be incident into the perovskite layer in the stacked solar cell through the first interface, and improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.
[0352] Based on any suitable embodiment of the present application, in some further embodiments, the atomic molar ratio of bromine element to iodine element in the first perovskite metal halide is (3 - y):y, where 0 < y ≤ 2; optionally, 1 ≤ y ≤ 2. Non-limiting examples of y may also include the following values: 0.3, 0.4, 0.5, 0.6, 2 / 3, 0.7, 0.75, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 1.9, 2, etc., and may also be selected from the intervals formed by any two of the above values.
[0353] In some embodiments, the atomic molar ratio of bromine element to iodine element is 2:3. At this time, y is 1.8.
[0354] In some embodiments, the atomic molar ratio of bromine element to iodine element is 1:2. At this time, y is 2.
[0355] According to the composition design of the perovskite metal halide in the first perovskite layer, the atomic molar ratio of bromine element to iodine element in the perovskite precursor solution can be adjusted, thereby regulating the comprehensive performance of the short-circuit current density and photoelectric conversion efficiency of the tandem solar cell. By adjusting the atomic molar ratio of bromine element to iodine element in the perovskite metal halide in the first perovskite layer within the above range, the short-circuit current density of the tandem solar cell can be better improved, and it can also be used to improve the photoelectric conversion efficiency.
[0356] Non-limitingly, the chemical composition of the first perovskite metal halide is ABX3, where A is a monovalent cation, B is a divalent metal ion, and X is a halogen anion. Optionally, A in the first perovskite metal halide includes one or more of alkali metal ions, monovalent amine cations, and monovalent amidinium cations. Optionally, B in the first perovskite metal halide includes 2+ Be 2+ Mg 2+ Ca 2+ Sr 2+ Ba 2+ Zn 2+ Ge 2+ Fe 2+ Co 2+ and Ni 2+ one or more of them. Optionally, X in the first perovskite metal halide includes at least one of Br- and I-. As a non-limiting example, A in the first perovskite metal halide includes CH(NH2)2 + CH3NH3 + Li + Na + K + Rb+ and Cs + or one or more of them.
[0357] Non-limiting examples of monovalent amine cations are CH3NH3 + (methylamine, MA + ), ammonium (NH4 + ). Non-limiting examples of monovalent amidinium cations are NH2CH=NH2 + (formamidine, denoted as FA + ).
[0358] In some embodiments, A in the first perovskite-type metal halide includes CH(NH2)2 + , CH3NH3 + , Li + , Na + , K + , Rb + and Cs + or one or more of them.
[0359] In some embodiments, in the first perovskite-type metal halide, A includes CH(NH2)2 + and Cs + , B includes Pb 2+ , X includes Br - and I - , wherein the molar ratio of CH(NH2)2 + and Cs + is (1-a):a, where 0 < a < 1. Optionally, a is 0.3 to 0.9, and further optionally any one of the following values or a ratio composed of any two of the following values: 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc. In some of these embodiments, the molar ratio of CH(NH2)2 + and Cs + is 3:2. Further, the atomic molar ratio of bromine element and iodine element can be 2:3 or 1:2.
[0360] Non-limitingly, the chemical composition of the second perovskite-type metal halide is MNY3, where M is a monovalent cation, N is a divalent metal ion, and Y is a halogen anion. Optionally, M in the second perovskite-type metal halide includes one or more of alkali metal ions, monovalent amine cations, and monovalent amidinium cations. Optionally, N in the second perovskite-type metal halide includes one or more of Sn 2+ and Pb 2+ . Optionally, Y in the second perovskite-type metal halide includes I-.
[0361] In some embodiments, M in the second perovskite metal halide comprises CH(NH2) 2+ 、CH3NH3 + , Li + 、Na + , K + , Rb + and Cs + One or more of .
[0362] In some embodiments, in the second perovskite metal halide, M comprises CH(NH2)2 + and CH3NH3 + , N including Pb 2+ and Sn 2+ , Y includes I - , among which, CH(NH2)2 + and CH3NH3 + The molar ratio of Pb is 7:3. 2+ and Sn 2+ The molar ratio is 1:1.
[0363] The appropriate perovskite metal halide may be selected according to the performance of the perovskite film and the requirements of process control.
[0364] Based on any suitable embodiment in the present application, in some further embodiments, at least a portion of the perovskite grains in the first perovskite layer are through-type grains, and the two ends of the through-type grains along the longitudinal direction are respectively located on both side surfaces of the first perovskite layer.
[0365] When the perovskite grains in the first perovskite layer include penetrating grains along the thickness direction of the first perovskite layer (i.e., along the longitudinal direction), it means that these perovskite grains grow continuously in the longitudinal direction, and there are few cracks in the longitudinal cross-section of the first perovskite layer, presenting as large-sized grains penetrating in the longitudinal direction. At this time, the penetrating grains that penetrate the first perovskite layer in the longitudinal direction are conducive to smoother and more efficient transmission of carriers, which is conducive to reducing non-radiative recombination caused by grain interfaces, and improving the short-circuit current density and photoelectric conversion efficiency of the device.
[0366] In the present application, unless otherwise specified, the "lateral size" of the perovskite grains in the first perovskite layer refers to the maximum size of the grains in all directions in the transverse section of the first perovskite layer. Statistical analysis can be performed based on the longitudinal cross-sectional view and the transverse cross-sectional view of the first perovskite layer. The longitudinal cross-sectional view and the transverse cross-sectional view of the first perovskite layer can be obtained by scanning electron microscopy technology, optical microscopy technology and other methods. According to the grain width in the longitudinal cross-sectional view, the transverse size of the grains can be semi-quantitatively analyzed, and quantitative statistical analysis data of the transverse size of the grains can also be obtained by analyzing the longitudinal cross-sectional views at different positions and directions. According to the transverse cross-sectional view, the transverse size of the grains can be quantitatively counted.
[0367] In the present application, when performing statistical analysis on the grain size in the first perovskite layer, the amount of data collected is appropriately selected based on the shape, size, uniformity, distribution pattern, etc. of the grains. For example, the minimum amount of data collected can be determined by controlling the standard deviation of the average value ≤ 10% of the average value.
[0368] Based on any suitable embodiment in the present application, in some further embodiments, the lateral dimension of at least a portion of the through-type grains is ≥400nm; wherein the lateral direction is orthogonal to the longitudinal direction, and the lateral dimension of the through-type grains represents the maximum dimension of the grains in all directions in the lateral section.
[0369] In the present application, unless otherwise specified, the "at least a portion" in "at least a portion of the through-type grains" may be measured by the number of grains, the lateral area of the grains, or the volume of the grains. In terms of quantity, "at least a portion" may represent greater than or equal to any of the following percentages: 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc.
[0370] Without limitation, the lateral size of at least a portion of the through-type grains may also satisfy any of the following sizes: 0.4 μm, 400 nm, 0.5 μm, 500 nm, 0.6 μm, 600 nm, 0.7 μm, 0.8 μm, 800 nm, 0.9 μm, 1.0 μm, 1.2 μm, etc. In some embodiments, the lateral size of at least a portion of the through-type grains is ≥ 0.400 nm, and may be ≥ 500 nm.
[0371] Without limitation, the lateral dimension of at least a portion of the through-type grains may also be selected from any one of the following sizes or from a range consisting of any two of the following sizes: 0.4μm, 400nm, 0.5μm, 500nm, 0.6μm, 600nm, 0.7μm, 0.8μm, 800nm, 0.9μm, 1.0μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, etc.
[0372] In a non-limiting manner, the average lateral size of the through-type grains is 300nm to 2μm, optionally 400nm to 1μm, and further optionally 500nm to 800nm. The average lateral size of the through-type grains can also be selected from any of the following sizes or from an interval consisting of any two of the following sizes: 0.3μm, 400nm, 0.3μm, 400nm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, etc.
[0373] By controlling the lateral size of the through-type grains, the number of interfaces between the perovskite grains can be adjusted. The larger the lateral size, the fewer the through-seams between the grains, and the fewer defects and higher quality of the corresponding perovskite layer. By controlling the lateral size of the through-type grains within the above range, it is beneficial to give full play to the promoting effect of the through-type grains.
[0374] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the width region of the longitudinal cross section of the first perovskite layer, the area percentage of the through-type grains relative to the longitudinal cross section is ≥80%, and can be ≥90%. The area percentage of the through-type grains relative to the longitudinal cross section can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any two of the following percentages: 80%, 85%, 90%, 95%, etc. Optionally, at least a portion of the width region of the longitudinal cross section of the first perovskite layer corresponds to a width region of at least 10 μm.
[0375] By controlling the area ratio of the through-type grains in the longitudinal section of the first perovskite layer, the role of the through-type grains can be adjusted. When the area ratio of the through-type grains relative to the longitudinal section of the first perovskite layer is controlled within the above range, it is beneficial to give full play to the advantages of the through-type grains and to improve the carrier transmission and photoelectric conversion efficiency.
[0376] Based on any suitable embodiment in the present application, in some further embodiments, on the longitudinal cross section of the first perovskite layer, the area percentage of the through-type grains with a lateral size of ≥400nm relative to the longitudinal cross section is ≥80%, and can be ≥90%. The area percentage of the through-type grains with a lateral size of ≥600nm relative to the longitudinal cross section can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any two of the following percentages: 80%, 85%, 90%, etc.
[0377] By controlling the area ratio of the larger through-type grains in the longitudinal section of the first perovskite layer, the role of the through-type grains can be adjusted. When the area ratio of the through-type grains with a certain lateral size relative to the longitudinal section of the first perovskite layer is controlled within the above range, it is beneficial to give full play to the advantages of the through-type grains and to improve the carrier transmission and photoelectric conversion efficiency.
[0378] Figure 4 FIG. 1 is a scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell in one embodiment of the present application. Figure 5 This is a scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell in another embodiment of the present application. In the first perovskite layer, a large number of longitudinal through-type grains can be observed, and the lateral size is large, and there are few broken crystals in the first perovskite layer. In addition, Figure 4 and Figure 5 In the embodiment shown, the second perovskite layer is also prepared by vacuum flash evaporation. Similarly, a large number of longitudinal through-type grains can be observed in the second perovskite layer, and the lateral size is large, and there are few broken crystals in the second perovskite layer.
[0379] Fig. 9 This is a scanning electron microscope (SEM) image of a longitudinal cross-section of a stacked solar cell prepared by the anti-solvent method in a comparison of the present application. The first perovskite layer is prepared by the anti-solvent method, and the surface of the first perovskite layer away from the first electrode is a flat and smooth surface, and the first electrode is a transparent electrode. Fig. 9 In the comparative example, no obvious wrinkles were observed between the wide-bandgap perovskite layer and the narrow-bandgap perovskite layer through optical microscope observation of the transparent electrode layer of the stacked solar cell. Fig. 9 In the first perovskite layer, there are fewer longitudinal through-type grains, more broken crystals, and smaller lateral sizes of the grains. According to the grain area analysis in the longitudinal section of the first perovskite layer, the longitudinal through-type grains are Fig. 9 The area ratio of the first perovskite layer is less than 50%.
[0380] In some embodiments, the thickness of the first perovskite layer may be 300 nm to 500 nm, and may further be 400 nm.
[0381] In some embodiments, the thickness of the second perovskite layer may be 300 nm to 500 nm, and may further be 400 nm.
[0382] In some embodiments, see Fig.11The stacked solar cell 10 includes a substrate layer 100, a first perovskite sub-cell 200, a carrier recombination layer 410 and a second perovskite sub-cell 600 which are stacked in sequence; wherein the first perovskite sub-cell 200 includes a first electrode 220, a first carrier transport layer 230, a first perovskite layer 240 and a second carrier transport layer 250 which are stacked in sequence, and the second perovskite sub-cell 600 includes a third carrier transport layer 630, a second perovskite layer 640, a fourth carrier transport layer 650 and a second electrode 660 which are stacked in sequence; wherein the first electrode 220, the first carrier transport layer 230, the first perovskite layer 240, the second carrier transport layer 250, the carrier recombination layer 410, the third carrier transport layer 630, the second perovskite layer 640, the fourth carrier transport layer 650 and the second electrode 660 are stacked in sequence. At this time, the second carrier transport layer 250 is located between the first perovskite layer 240 and the carrier recombination layer 410, and the third carrier transport layer 630 is located between the carrier recombination layer 410 and the second perovskite layer 640. Among them, the second carrier transport layer 250, the carrier recombination layer 410 and the third carrier transport layer 630 constitute the intermediate interconnection layer 400, and the interface between the intermediate interconnection layer 400 and the first perovskite layer 240 corresponds to the aforementioned first interface. Further, the second carrier transport layer and the third carrier transport layer on both sides of the carrier recombination layer are heterogeneous carrier transport layers, one is an electron transport layer, and the other is a hole transport layer. One of the first carrier transport layer and the second carrier transport layer is an electron transport layer, and the other is a hole transport layer. One of the third carrier transport layer and the fourth carrier transport layer is an electron transport layer, and the other is a hole transport layer. Therefore, the first carrier transport layer and the third carrier transport layer are both electron transport layers or both hole transport layers, and correspondingly, the second carrier transport layer and the fourth carrier transport layer are both hole transport layers or both electron transport layers.
[0383] In some embodiments, the first carrier transport layer and the third carrier transport layer are both electron transport layers, and the second carrier transport layer and the fourth carrier transport layer are both hole transport layers.
[0384] In other embodiments, the first carrier transport layer and the third carrier transport layer are both hole transport layers, and the second carrier transport layer and the fourth carrier transport layer are both electron transport layers.
[0385] In some embodiments, a perovskite-based tandem solar cell includes a first electrode and a second electrode, one of which is a positive electrode and the other is a negative electrode. The first electrode is located at one end of the first perovskite subcell away from the carrier recombination layer, and the second electrode is located at one end of the second perovskite subcell away from the carrier recombination layer. The positive electrode can collect electron carriers transmitted via the electron transport layer. The negative electrode can collect hole carriers transmitted via the hole transport layer.
[0386] At least one of the first electrode and the second electrode is a transparent electrode for light incidence. In some embodiments, the first electrode is a transparent electrode.
[0387] In some embodiments, one of the first electrode and the second electrode is a transparent electrode, and the other is a metal electrode. In some embodiments, the first electrode is a transparent electrode, and the second electrode is a metal electrode.
[0388] Without limitation, the tandem solar cell based on tandem perovskite further comprises a substrate layer. The substrate may be disposed on the side of the first electrode facing away from the carrier recombination layer, or may be disposed on the side of the second electrode facing away from the carrier recombination layer. In some embodiments, the tandem cell comprises a substrate layer, a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell disposed in sequence. In some embodiments, the tandem cell comprises a substrate layer, a first electrode, a first carrier transport layer, a first perovskite layer, a second carrier transport layer, a carrier recombination layer, a third carrier transport layer, a second perovskite layer, a fourth carrier transport layer, and a second electrode disposed in sequence. In some embodiments, the stacked battery includes a substrate layer, a first electrode, a first carrier transport layer, a first perovskite layer, an intermediate interconnect layer, a second perovskite layer, a fourth carrier transport layer, and a second electrode arranged in sequence, the intermediate interconnect layer may include a second carrier transport layer, a carrier recombination layer, and a third carrier transport layer, the second carrier transport layer is located between the first perovskite layer and the carrier recombination layer, and the third carrier transport layer is located between the carrier recombination layer and the second perovskite layer. Further, the second carrier transport layer and the third carrier transport layer on both sides of the carrier recombination layer are heterogeneous carrier transport layers, one is an electron transport layer, and the other is a hole transport layer.
[0389] The substrate layer involved in the embodiments or examples of the present application may be, but is not limited to, a glass substrate or a flexible substrate. In a non-limiting manner, the flexible substrate may include one or more materials selected from polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyethylene naphthalate, etc. Unless otherwise specified, the substrate layer is a transparent substrate.
[0390] In some embodiments, the substrate layer is a flexible substrate layer. Further, the material of the substrate layer may be, for example (but not limited to), an organic polymer material, and further, may be mixed in different proportions with one or more of the following materials: including but not limited to polyvinyl alcohol (PVA), polyester (PET), polyimide (PI), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), etc.
[0391] Taking the first electrode as a transparent electrode, and the transparent substrate layer being located on the side of the first electrode away from the carrier recombination layer, that is, on the side of the first perovskite sub-cell as an example, at this time, when the stacked solar cell based on stacked perovskite is working, part of the incident light is absorbed by the first perovskite layer, and part of the incident light passes through the first perovskite layer and the first interface and is absorbed by the second perovskite layer. After the two perovskite light-absorbing layers receive photons, the internal electrons gain energy and break free from the constraints of the light-absorbing layers to form negatively charged electron carriers, and at the same time form positively charged hole carriers, thereby obtaining electron-hole pairs, and free electrons and free holes are transmitted in opposite directions through the corresponding transport layers, so that electrons and holes flow, wherein the second carrier transport layer and the third carrier transport layer on both sides of the carrier recombination layer are electron transport layers and hole transport layers, respectively. Electrons and holes from both sides of the carrier recombination layer recombine in the carrier recombination layer, so that the first perovskite sub-cell and the second perovskite sub-cell are connected in series, thereby forming an electric current in the stacked solar cell and realizing the conversion of light energy into electrical energy.
[0392] When the first carrier transport layer and the third carrier transport layer are both electron transport layers, and the second carrier transport layer and the fourth carrier transport layer are both hole transport layers, free electrons are collected by the first electrode via the first carrier transport layer, and free holes are collected by the second electrode via the fourth carrier transport layer, thereby forming an optical circuit in the stacked solar cell.
[0393] The electron transport layer can extract and transport electron carriers and block the passage of free holes.
[0394] The hole transport layer can extract and transport hole carriers and block the passage of free electrons.
[0395] In some embodiments, the material of the transparent electrode may be exemplified by, but not limited to, one or more of the following materials: FTO (fluorine-doped tin oxide), ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), BZO (boron-doped zinc oxide), IZO (indium zinc oxide), IWO (tungsten-doped indium oxide), etc.
[0396] In some embodiments, the transparent electrode mainly includes a transparent conductive material, and the transparent conductive material may include a transparent conductive oxide. Without limitation, the transparent conductive oxide in the transparent electrode may include one or more of indium tin oxide, fluorine-doped tin oxide, indium-doped tungsten oxide, indium-doped zinc oxide, and aluminum-doped zinc oxide.
[0397] In some embodiments, the metal electrode mainly includes a metal material, and the metal material may include one or more of gold, silver, copper, aluminum, nickel, chromium, bismuth, platinum, magnesium, molybdenum, tungsten, and the like.
[0398] In this application, when it comes to components, "mainly including one or more of substances a1, a2, ..., etc.", unless otherwise specified, "mainly including" means that the mass percentage is at least 80%, and can also be ≥90%, ≥95%, ≥98%, etc., or 100%. When the mass percentage is 100%, "mainly including one or more of substances a1, a2, ..., etc." means that it is composed of one or more of substances a1, a2, ..., etc.
[0399] In some embodiments, the electron transport material in the electron transport layer of the first perovskite subcell (which may be referred to as the first electron transport material) includes an N-type semiconductor. The first electron transport material may include, but is not limited to, one or more of the following materials: bathocuproin, [6,6]-phenyl-C 61 -Isomethyl butyrate, [6,6]-phenyl C 71 -Methyl butyrate, C 60 , C 70 , tin oxide (SnO x , the value of x can range from 1.5 to 2), zinc oxide and its derivatives, and modified products of any of the foregoing materials after doping or passivation.
[0400] In some embodiments, the hole transport material in the hole transport layer of the first perovskite subcell (which may be recorded as the first hole transport material) includes a P-type semiconductor. The first hole transport material may include, but is not limited to, one or more of the following materials: [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly-3-hexylthiophene, triphenylamine with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine, N-(4-aniline)carbazole-spirobifluorene, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), polythiophene, nickel oxide, molybdenum oxide, cuprous iodide, cuprous oxide and its derivatives, and any of the above materials doped or passivated modified materials, phosphoric acid carbazole materials, etc.
[0401] Without limitation, the material of the carrier recombination layer may include at least one of a transparent conductive oxide and a metal element. Without limitation, the transparent conductive oxide in the carrier recombination layer may include one or more of indium tin oxide, fluorine-doped tin oxide, indium-doped tungsten oxide, indium-doped zinc oxide, and aluminum-doped zinc oxide. The metal element in the carrier recombination layer may include one or more of gold, silver, copper, aluminum, nickel, chromium, bismuth, platinum, magnesium, molybdenum, tungsten, etc.
[0402] In some embodiments, the electron transport material in the electron transport layer of the second perovskite subcell (which may be referred to as the second electron transport material) includes an N-type semiconductor. The second electron transport material may include, but is not limited to, one or more of the following materials: bathocuproin, [6,6]-phenyl-C 61 -Isomethyl butyrate, [6,6]-phenyl C 71 -Methyl butyrate, C 60 , C 70 , tin oxide (SnO x , the value of x can range from 1.5 to 2), zinc oxide and its derivatives, and modified products of any of the foregoing materials after doping or passivation.
[0403] In some embodiments, the hole transport material in the hole transport layer of the second perovskite subcell (which may be recorded as the second hole transport material) includes a P-type semiconductor. The second hole transport material may include, but is not limited to, one or more of the following materials: [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly-3-hexylthiophene, triphenylamine with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine, N-(4-aniline)carbazole-spirobifluorene, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), polythiophene, nickel oxide, molybdenum oxide, cuprous iodide, cuprous oxide and its derivatives, and any of the above materials doped or passivated modified materials, phosphoric acid carbazole materials, etc.
[0404] Based on any suitable embodiment in the present application, in some further embodiments, a heterogeneous carrier blocking layer is provided on at least one side of one or more carrier transport layers among the first carrier transport layer, the second carrier transport layer, the third carrier transport layer and the fourth carrier transport layer.
[0405] In some embodiments, see Fig.12The stacked solar cell 10 includes a substrate layer 100, a first perovskite sub-cell 200, a carrier recombination layer 410, and a second perovskite sub-cell 600, which are stacked in sequence; wherein the first perovskite sub-cell 200 includes a first electrode 220, a first carrier transport layer 230, a first perovskite layer 240, and a second carrier transport layer 250, which are stacked in sequence, and the second perovskite sub-cell 600 includes a third carrier transport layer 630, a second perovskite layer 640, a fourth carrier transport layer 650, and a second electrode 660, which are stacked in sequence; wherein the first electrode 220, the first carrier transport layer 230, The first perovskite layer 240, the second carrier transport layer 250, the carrier recombination layer 410, the third carrier transport layer 630, the second perovskite layer 640, the fourth carrier transport layer 650 and the second electrode 660 are stacked in sequence; wherein the fourth carrier transport layer and the second carrier transport layer are both electron transport layers, and the third carrier transport layer and the first carrier transport layer are both hole transport layers; the side of the fourth carrier transport layer 650 close to the second perovskite layer 640 includes a second hole blocking layer 6501, and the side of the second carrier transport layer 250 close to the first perovskite layer 240 includes a first hole blocking layer 2501. The second carrier transport layer 250, the carrier recombination layer 410 and the third carrier transport layer 630 constitute the intermediate interconnection layer 400, and the interface between the intermediate interconnection layer 400 and the first perovskite layer 240 corresponds to the aforementioned first interface.
[0406] Based on any suitable embodiment of the present application, in some further embodiments, any one of the first carrier transport layer, the second carrier transport layer, the third carrier transport layer and the fourth carrier transport layer can be independently provided with a heterogeneous carrier blocking layer. In some of the embodiments, any of the aforementioned transport layers can be independently provided on at least one side of the transport layer.
[0407] Based on any suitable embodiment of the present application, in some further embodiments, the stacked solar cell satisfies one or more of the following features (the reference in any of the following features can also be selected from any suitable numerical value or range in the context):
[0408] The first carrier transport layer and the third carrier transport layer are both electron transport layers, and the second carrier transport layer and the fourth carrier transport layer are both hole transport layers, or the first carrier transport layer and the third carrier transport layer are both hole transport layers, and the second carrier transport layer and the fourth carrier transport layer are both electron transport layers;
[0409] The stacked solar cell further comprises a first electrode and a second electrode, wherein the first electrode is located on a side of the first perovskite subcell away from the carrier recombination layer, and the second electrode is located on a side of the second perovskite subcell away from the carrier recombination layer; the first electrode is a transparent electrode;
[0410] At least one side of the first carrier transport layer includes a heterogeneous carrier blocking layer;
[0411] At least one side of the second carrier transport layer includes a heterogeneous carrier blocking layer;
[0412] At least one side of the third carrier transport layer comprises a heterogeneous carrier blocking layer;
[0413] At least one side of the fourth carrier transport layer includes a foreign carrier blocking layer.
[0414] The first perovskite sub-cell and the second perovskite sub-cell may both be nip-type or both be pin-type.
[0415] When the first electrode is a transparent electrode, the incident light entering the stacked solar cell can be incident from the first electrode side. At this time, when the incident light is first emitted from the first perovskite layer side to the first interface, the first interface is conducive to achieving the aforementioned effect of improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.
[0416] In addition, a heterogeneous carrier blocking layer may be provided on at least one side of one or more of the first carrier transport layer, the second carrier transport layer, the third carrier transport layer and the fourth carrier transport layer to block the transport of heterogeneous carriers, thereby facilitating the reduction of the recombination probability of electrons and holes.
[0417] In some embodiments, the hole blocking layer in the first perovskite subcell (which may be referred to as the first hole blocking layer) is composed of materials including fullerene and its derivatives, SnO x One or more of, wherein the value of x ranges from 1.5 to 2. Non-limiting examples of fullerenes may include one or more of C60, C61, C70, and the like.
[0418] In some embodiments, the hole blocking layer in the second perovskite subcell (which may be referred to as the second hole blocking layer) is composed of materials including fullerene and its derivatives, SnO x One or more of, wherein the value of x ranges from 1.5 to 2. Non-limiting examples of fullerenes may include one or more of C60, C61, C70, and the like.
[0419] In some embodiments, the thickness of the electron transport layer may be 20 nm.
[0420] In some embodiments, when the respective blocking layers are present, the thickness of the first hole blocking layer and the second hole blocking layer are each independently 10 nm.
[0421] In some embodiments, the hole transport layer may have a thickness of 20 nm.
[0422] Based on any suitable embodiment in the present application, in some further embodiments, the first perovskite sub-cell and the second perovskite sub-cell form an integrated structure with two ends.
[0423] Based on any suitable implementation in the present application, in some further implementations, the stacked solar cell is a two-end stacked solar cell.
[0424] Based on any suitable embodiment in the present application, in some further embodiments, the tandem solar cell is an all-perovskite tandem solar cell.
[0425] In a tandem solar cell including a perovskite layer, taking the full perovskite tandem solar cell in which the first perovskite subcell is a wide bandgap perovskite subcell and the second perovskite subcell is a narrow bandgap perovskite subcell as an example, the conventional preparation method is to first prepare a wide bandgap perovskite layer on the carrier transport layer by a solvent method, and then deposit the functional layers and narrow bandgap perovskite layers of the intermediate interconnect layer layer by layer, wherein the solvent in the functional layer other than the perovskite layer (such as the carrier transport layer) is usually removed by a thermal evaporation method, and multiple high-temperature processes are required. The accumulation of these high-temperature processes is equivalent to annealing the wide bandgap perovskite layer in the bottom cell, which easily leads to a decrease in the photoelectric conversion efficiency of the bottom wide bandgap perovskite subcell. In some embodiments, the third carrier transport layer is prepared by a vacuum flash evaporation process, and the high temperature treatment process of the first perovskite layer is conducive to reducing the efficiency attenuation effect of the subsequent process on the first perovskite layer subcell. In some further embodiments, the third carrier layer and the second perovskite layer are both prepared by a vacuum flash evaporation process.
[0426] In this application, unless otherwise specified, any perovskite layer in a perovskite-based tandem solar cell can be disassembled in the following manner and then the surface of the perovskite layer can be tested and analyzed: Taking the electron transport layer as C60 / BCP, the second electrode is located on the surface of the electron transport layer away from the light absorption layer and is a Cu electrode as an example, the tandem solar cell can be disassembled, the first electrode and the second electrode (such as the Cu electrode) can be removed, and the electron transport layer (such as C60 / BCP) can be washed away with the anti-solvent (such as chlorobenzene) of the corresponding perovskite layer. The second electrode can be removed by, for example, using tape to remove it.
[0427] It can be understood that the structure of the perovskite subcell involved in the present application may not be limited to the structural layers listed above. Other functional layers, such as buffer layers and insertion layers, may also be introduced as required. In some embodiments, the perovskite subcell may be provided with a buffer layer with a suitable energy level, which may play a role in reducing energy level barriers, promoting energy level matching, improving carrier extraction efficiency, and at the same time passivating interface defect states, protecting light absorption layers, inhibiting water molecules, oxygen oxidation and decomposition of batteries, improving photoelectric conversion efficiency, and improving the stability of perovskite subcells and stacked solar cells. One or more of the above. Depending on the location of the buffer layer, the type of buffer layer may include a buffer layer between the hole transport layer and the anode, a buffer layer between the electron transport layer and the cathode, a buffer layer between the hole transport layer and the absorption layer, and a buffer layer between the electron transport layer and the absorption layer. The materials that can be used for the buffer layer in the stacked solar cell may include, but are not limited to, Cu2O, NiO, AZO, TiO2, etc. In some embodiments, an insertion layer may be provided between the electron transport layer and the adjacent electrode, and an example of the material of the insertion layer may be bathocuproine (BCP).
[0428] In a second aspect of the present application, a method for preparing the perovskite-based tandem solar cell according to the first aspect of the present application is provided, comprising the following steps: sequentially stacking a first carrier transport layer, a first perovskite layer, a second carrier transport layer, a carrier recombination layer, a third carrier transport layer, a second perovskite layer, a fourth carrier transport layer and a second electrode on a surface of one side of a first electrode to prepare the perovskite-based tandem solar cell;
[0429] The method of stacking the first perovskite layer on the side of the first carrier transport layer facing away from the first electrode comprises the following steps:
[0430] Applying the precursor solution I of the first perovskite layer to the surface of the first carrier transport layer on the side away from the first electrode to form a coating layer I;
[0431] The coating layer I is subjected to vacuum flash evaporation treatment and annealing treatment to form the first perovskite layer, and the non-smooth surface is formed on a side of the first perovskite layer away from the first electrode.
[0432] By preparing the first perovskite layer through the vacuum flash evaporation process, the aforementioned concave grooves and convex ridges can be formed on the surface of the first perovskite layer close to the carrier recombination layer, increasing the amount of photons in contact with the perovskite layer and the light utilization rate, improving the short-circuit current density of the stacked solar cell, and improving the photoelectric conversion efficiency. In addition, it can also promote the formation of large-sized through-type grains, promote carrier transmission and photoelectric conversion efficiency.
[0433] Principle of preparing perovskite layer by vacuum flash evaporation treatment: After the wet film of perovskite is spin-coated and placed in a vacuum flash evaporation device, the atmosphere in the device is evacuated by a vacuum pump, making the internal air pressure much lower than the atmospheric pressure, thereby reducing the saturated vapor pressure of the solvent in the perovskite wet film. Within a few seconds, the boiling point of the solvent in the perovskite wet film will be reduced below room temperature, so that it evaporates from the wet film and is continuously evacuated, thus achieving the effect of removing the solvent and rapidly crystallizing.
[0434] Non-limitingly, the precursor solution of any perovskite layer can be prepared by the following method: Prepare the perovskite precursor materials according to the stoichiometric ratio of perovskite-type metal halides in the perovskite layer, dissolve the perovskite precursor materials in a solvent to form a mixed solution, stir for 1 h, and filter with a 0.22 μm organic filter membrane to obtain the perovskite precursor solution. In this application, unless otherwise specified, the perovskite precursor solution is the perovskite precursor solution.
[0435] Taking the precursor solution for preparing the first perovskite layer as an example, taking the perovskite-type metal halide as Cs a FA 1-a PbI 3-y Br y (0 < a < 1, 0 < y ≤ 1.2) as an example, the perovskite precursor materials can be a combination of lead iodide, lead bromide, formamidinium bromide, formamidinium iodide, cesium iodide and cesium bromide, and the active substance of the perovskite absorption layer is the CsFA system.
[0436] Non-limitingly, in the process of preparing the first perovskite layer, the preparation method can further meet one or more of the following characteristics:
[0437] The vacuum flash evaporation treatment is carried out under negative pressure conditions. Optionally, the negative pressure conditions are ≤ 100 Pa, and further optionally 50 Pa - 100 Pa;
[0438] The temperature for carrying out the vacuum flash evaporation treatment is -10 °C - 100 °C, optionally 0 °C - 30 °C, and further optionally 20 °C - 30 °C;
[0439] The duration of carrying out the vacuum flash evaporation treatment is 10 s - 100 s, optionally 10 s - 30 s, and further optionally 15 s - 25 s;
[0440] The annealing treatment is carried out by a hot stage method. Optionally, a 30 °C - 200 °C hot stage is used, further optionally a 90 °C - 110 °C hot stage, and even more optionally a 98 °C - 102 °C hot stage;
[0441] The annealing duration for carrying out the annealing treatment is 30 s - 60 min, optionally 5 min - 20 min, and further optionally 14 min - 16 min.
[0442] Based on any suitable embodiment of the present application, in some further embodiments, the step of coating the precursor solution I of the first perovskite layer onto the surface of the first carrier transport layer on the side away from the first electrode comprises:
[0443] Spin coating a portion of the precursor solution I onto a surface of the first carrier transport layer that is away from the first electrode at a first rotation speed;
[0444] Accelerating the rotation speed from the first rotation speed to a second rotation speed, and continuing to spin-coat another portion of the precursor liquid I at the second rotation speed;
[0445] Wherein, the second rotation speed is greater than the first rotation speed.
[0446] Based on any suitable embodiment of the present application, in some further embodiments, in the process of preparing the first perovskite layer, the preparation method satisfies one or more of the following characteristics (the reference in any of the following characteristics can also be selected from any suitable value or range in the context):
[0447] The first rotation speed is 1000 rpm to 6000 rpm, and can be 1000 rpm to 2000 rpm; the spin coating is performed at the first rotation speed for 8 s to 12 s;
[0448] In the step of accelerating the rotation speed from the first rotation speed to the second rotation speed, the acceleration is 200 rpm / s to 2000 rpm / s, and can be optionally 800 rpm / s to 1200 rpm / s;
[0449] The second rotation speed is 3000 rpm to 4500 rpm, and can be optionally 3800 rpm to 4200 rpm; the spin coating is performed at the second rotation speed for 18 s to 22 s.
[0450] By adjusting one or more parameters in the preparation process of the first perovskite layer and regulating the surface morphology and / or grain size of the first perovskite layer as needed, the short-circuit current density and the comprehensive performance of the photoelectric conversion efficiency of the stacked solar cell can be better improved through process parameter optimization.
[0451] In some embodiments, the second perovskite layer is also prepared by vacuum flash evaporation, comprising the following steps: coating the precursor liquid II of the second perovskite layer on the surface of the third carrier transport layer away from the carrier recombination layer to form a coating layer II, performing vacuum flash evaporation on the coating layer II, and performing annealing to form the second perovskite layer. The coating layer II is subjected to vacuum flash evaporation, and the parameters of the annealing treatment can refer to the description of the coating layer I.
[0452] By preparing the second perovskite layer through the vacuum flash evaporation process, a concave groove and convex ridge morphology similar to the above can be formed on the surface of the second perovskite layer away from the carrier recombination layer, thereby increasing the chance of light secondary incident on the second perovskite layer, increasing light utilization, improving the photoelectric conversion efficiency of the stacked solar cell, and improving the short-circuit current density. In addition, it can also promote the formation of large-sized through-type grains, promote carrier transmission and photoelectric conversion efficiency.
[0453] Each structural layer other than the perovskite layer in the stacked solar cell can be prepared by one or more of the following methods, including but not limited to: chemical bath deposition, electrochemical deposition, chemical vapor deposition, thermal evaporation co-evaporation, atomic layer deposition, magnetron sputtering, precursor liquid spin coating, precursor liquid slit coating, precursor liquid scraping, mechanical pressing, etc. A suitable method can be selected according to the material properties of each structural layer to be stacked with adjacent structural layers. In some embodiments, each structural layer other than the perovskite layer in the stacked solar cell can be prepared by one or more of the following methods, including but not limited to: thermal evaporation, precursor liquid coating, etc., wherein the precursor liquid coating method can be a precursor liquid spin coating method.
[0454] Without limitation, the second perovskite layer may be prepared using vacuum flash evaporation process parameters similar to those used to prepare the first perovskite layer.
[0455] Based on any suitable embodiment of the present application, in some further embodiments, the precursor liquid II is subjected to vacuum flash evaporation treatment, and the annealing includes: vacuum flash evaporation treatment of the precursor liquid II under negative pressure conditions, and then annealing treatment under heating conditions;
[0456] Without limitation, in the process of preparing the second perovskite layer, the preparation method may further satisfy one or more of the following characteristics (the reference in any of the following characteristics may also be selected from any suitable value or range in the context):
[0457] The negative pressure condition is less than or equal to 100Pa (≤100Pa), and can be selected as 50Pa~100Pa;
[0458] The temperature of the vacuum flash treatment is -10°C to 100°C, optionally 0°C to 30°C, and further optionally 20°C to 30°C;
[0459] The vacuum flash treatment time is 10s to 100s, optionally 10s to 30s, and further optionally 15s to 25s;
[0460] The heating condition adopts a 30°C to 200°C hot stage, optionally a 90°C to 110°C hot stage, and further optionally, a 98°C to 102°C hot stage;
[0461] The annealing time of the annealing treatment is 30s to 60min, optionally 5min to 20min, and further optionally 8min to 12min.
[0462] Based on any suitable embodiment of the present application, in some further embodiments, the step of coating the precursor solution II of the second perovskite layer onto the surface of the third carrier transport layer facing away from the carrier recombination layer comprises:
[0463] Spin coating a portion of the precursor solution II at a third rotation speed onto a surface of the third carrier transport layer on a side away from the carrier recombination layer;
[0464] Accelerating the rotation speed from the third rotation speed to a fourth rotation speed, and continuing to spin-coat another portion of the precursor liquid II at the fourth rotation speed;
[0465] Wherein, the fourth rotational speed is greater than the third rotational speed.
[0466] Based on any suitable embodiment of the present application, in some further embodiments, during the preparation of the first perovskite layer, the preparation method satisfies one or more of the following characteristics (the reference in any of the following characteristics can also be selected from any suitable value or range in the context):
[0467] The third rotation speed is 1000 rpm to 6000 rpm, and can be 1000 rpm to 2000 rpm; the spin coating is performed at the third rotation speed for 8 s to 12 s;
[0468] In the step of accelerating the rotation speed from the third rotation speed to the fourth rotation speed, the acceleration is 200 rpm / s to 2000 rpm / s, and can be optionally 800 rpm / s to 1200 rpm / s;
[0469] The fourth rotation speed is 3000 rpm to 4500 rpm, and can be optionally 3800 rpm to 4200 rpm; the spin coating is performed at the fourth rotation speed for 18s to 22s.
[0470] In some embodiments, taking the example of the substrate layer being located on the side of the first perovskite subcell away from the carrier recombination layer, and taking the example of preparing each structural layer layer by layer on the first substrate including the substrate layer and the first electrode, one or more structural layers in each structural layer from the first perovskite layer to the second electrode in the stacked solar cell are prepared by a vacuum flash evaporation method. At this time, after the non-smooth surface of the first perovskite layer away from the first electrode is formed, the thermal evaporation process is reduced, which can help reduce the adverse effects of conventional thermal annealing processes on the photoelectric conversion efficiency of the first perovskite layer.
[0471] In some embodiments, other structural layers in the stacked solar cell except the structural layer prepared by the vacuum flash evaporation process can be prepared by evaporation. For example, the first electrode and the first carrier transport layer can both be prepared by the evaporation process.
[0472] In a third aspect of the present application, an electrical device is provided, comprising at least one of the perovskite-based tandem solar cells described in the first aspect of the present application and the perovskite-based tandem solar cells prepared by the preparation method described in the second aspect of the present application.
[0473] In some embodiments, the stacked solar cell can be used as a power generation device of an electrical device. The type of the power generation device can include but is not limited to integrated power generation. The location of the power generation device can include but is not limited to the roof, back panel, etc. of a car.
[0474] Furthermore, the above-mentioned electrical devices may include mobile devices, such as mobile phones, laptop computers, etc., electric vehicles, electric trains, ships and satellites, power generation systems, etc., but are not limited thereto.
[0475] Fig.13 The power consumption device 6 is an automobile, and can further be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0476] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, a calculator, etc.
[0477] As another example, the power-consuming device may be a wearable device, such as a watch.
[0478] Below, some embodiments of the present application are described. The embodiments described below are exemplary, are only used to explain the present application, and cannot be construed as limiting the present application. In the embodiments, if the technology or conditions are not indicated, they are carried out according to the description above, or according to the technology or conditions described in the document in this area or according to the product specification. The reagents used or the instruments that do not indicate the manufacturer are conventional products that can be obtained commercially, or can be synthesized in a conventional manner by commercially available products.
[0479] In the following examples, room temperature refers to 20°C to 30°C.
[0480] Preparation method of perovskite-based tandem solar cells: The first perovskite layer and the second perovskite layer are prepared by vacuum flash evaporation, and both perovskite sub-cells are inverted pin type. The first perovskite layer is a wide bandgap perovskite layer, and the bandgap satisfies 1.2eV to 2.4eV, and also satisfies 1.6eV to 2.3eV; the second perovskite layer is a narrow bandgap perovskite layer, and the bandgap satisfies 1.0eV to 1.4eV.
[0481] S10, clean the glass on which the transparent conductive film ITO has been deposited, and use acetone, alcohol, and deionized water to clean it in sequence to obtain the first electrode; after drying, it is ready for the next step. The base layer is a glass base, and the ITO layer is used as the first electrode. The length × width × height of the first electrode is 20mm × 15mm × 200nm.
[0482] S20, spin coating the ethanol solution of MeO-4PACz onto the surface of the first electrode of the first substrate at a spin coating speed of 4000 rpm and a spin coating time of 30 s; then transfer to a hot stage and anneal at 100° C. for 10 min to form a hole transport layer (first carrier transport layer) on the surface of the first electrode with a thickness of 1 nm.
[0483] Wherein, MeO-4PACz is [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and the ethanol solution of MeO-4PACz is prepared by the following method: 0.3 mg of MeO-4PACz is added to 1 mL of ethanol and stirred evenly.
[0484] S30, adding 85 μL of the first perovskite precursor solution to the surface of the hole transport layer formed in step S20 at a speed of 1000 rpm to 2000 rpm, rotating for 10 seconds, then increasing the speed to 4000 rpm with an acceleration of 1000 rpm / s, and spin coating for 20 seconds at a speed of 4000 rpm, then transferring to a vacuum flash chamber, and pumping the pressure in the chamber to below 100 Pa (room temperature, about 60 Pa) with a vacuum pump, and then maintaining it for 20 seconds. After the vacuum flash treatment is completed, the multilayer film is annealed on a hot stage at 100°C for 15 minutes to form a first perovskite layer, also recorded as a wide bandgap perovskite layer, with a thickness of about 400 nm.
[0485] Among them, the precursor solution of the first perovskite layer is also recorded as a wide bandgap perovskite precursor solution or a first perovskite precursor solution, and is prepared by the following method: the perovskite precursor material is added to 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 3:1, stirred at 600 rpm on a magnetic stirrer for 2 hours, and filtered for standby use.
[0486] Taking Example 1 as an example, the precursor solution of the first perovskite layer is prepared by the following method: 123 mg FAI (formamidine iodide), 59 mg FABr (formamidine bromide), 46 mg CsI (cesium iodide), 25 mg CsBr (cesium bromide), 428 mg PbI2 (lead iodide) and 209 mg PbBr2 (lead bromide) of the perovskite precursor material are added to 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 3:1, stirred at 600 rpm on a magnetic stirrer for 2 hours, filtered and set aside. The chemical formula of the corresponding perovskite material is Cs a FA 1-a PbI 3-y Br y , where a is 0.4 and y is 2.
[0487] S40, vapor-depositing a 20 nm thick C60 layer on the wide bandgap perovskite layer prepared in step S30 to form a C60 film layer as an electron transport layer (second carrier transport layer).
[0488] S50, using an ALD device (atomic layer deposition device) to prepare a 20 nm SnO layer on the C60 film layer prepared in step S40 by an atomic layer deposition process. x (1.5≤x≤2), as the first hole blocking layer. In this example, the second carrier transport layer is composed of a 20nm thick C60 film layer prepared in steps S40 and S50 and a 20nm thick SnO x (1.5≤x≤2) film layer composition.
[0489] S60, the SnO prepared in step S50 x Au with a thickness of about 1 nm is evaporated on the film layer as a carrier recombination layer.
[0490] S70, spin coating a solution of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) on the carrier composite layer prepared in step S60, with the solvent being water, the spin coating speed being 4000 rpm, and the spin coating time being 30 s; then transferring to a hot stage and annealing at 150° C. for 10 min to form a PEDOT:PSS film layer (the third carrier transport layer, serving as a hole transport layer) with a thickness of about 20 nm.
[0491] S80, adding 100 μL of the second perovskite precursor solution onto the PEDOT:PSS film layer prepared in step S70 at a speed of 1000 rpm to 2000 rpm, rotating for 10 seconds, then increasing the speed to 4000 rpm at an acceleration of 1000 rpm / s, and spin coating for 20 seconds at a speed of 4000 rpm, then transferring to a vacuum flash chamber, and pumping the pressure in the chamber to below 100 Pa (60 Pa) with a vacuum pump, and maintaining for 20 seconds. After the vacuum flash treatment is completed, the multilayer film is annealed on a hot stage at 100°C for 10 minutes to form a second perovskite layer, also recorded as a narrow bandgap perovskite layer or a second perovskite precursor solution, with a thickness of about 700 nm.
[0492] The second perovskite precursor solution was prepared by the following method: the perovskite precursor material was added into 1 mL of a mixed solvent of DMF and DMSO in a volume ratio of 3:1, stirred at 600 rpm on a magnetic stirrer for 2 h, and filtered for standby use.
[0493] Taking Example 1 as an example, the second perovskite precursor solution is prepared by the following method: 216 mg of FAI, 85 mg of MAI, 414 mg of PbI2, 335 mg of SnI2 and 0.1 mg to 1 mg (0.6 mg in Example 1) of MeO-4PACz are added to 1 mL of a mixed solvent of DMF and DMSO with a volume ratio of 3:1, stirred at 600 rpm on a magnetic stirrer for 2 hours, filtered and set aside. In Example 1, the perovskite metal halide in the second perovskite precursor solution and the second perovskite layer is FA 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3.
[0494] S90, using an evaporation device to sequentially evaporate 25 nm thick C60, 10 nm thick BCP (bathocuproin) and 80 nm thick Cu on the narrow bandgap perovskite layer prepared in step S80, as an electron transport layer (third carrier transport layer), an insertion layer and a second electrode, respectively.
[0495] Example 2 adopts a method basically the same as Example 1 to prepare a stacked solar cell, and the operating processes of steps S10, S30, S40, S50, S60, S80 and S90 are the same as those of Example 1, except that: step S20 to prepare the hole transport layer and step S70 to prepare the PEDOT:PSS film layer both adopt a vacuum flash evaporation process.
[0496] S20: Spin-coat the ethanol solution of MeO-4PACz onto the first substrate prepared in step S10 at a spin-coating speed of 4000 rpm and a spin-coating time of 30 s; then transfer the solution into a vacuum flash chamber, pump the pressure in the chamber to below 100 Pa with a vacuum pump, and then maintain the pressure for 20 s.
[0497] S70: a PEDOT:PSS film layer is prepared on the carrier recombination layer prepared in step S60 by spin coating, with a spin coating speed of 4000 rpm and a spin coating time of 30 s; then the film is transferred to a vacuum flash chamber, the pressure in the chamber is pumped down to below 100 Pa by a vacuum pump, and then maintained for 20 s.
[0498] Examples 3 to 9 adopt substantially the same method as that of Example 1, and the preparation parameters can be found in Table 1. The only difference is the different composition of the perovskite metal halide.
[0499] Comparative Example 1. Preparation of the first perovskite layer and the second perovskite layer by anti-solvent method
[0500] Comparative Example 1 adopts a method substantially the same as Example 1, except that the method for preparing the first perovskite layer in S30 and the method for preparing the second perovskite layer in S80 are different, both of which adopt the anti-solvent method.
[0501] S30 used the anti-solvent method to prepare the first perovskite layer: 123 mg of CH(NH2)2I, 59 mg of CH(NH2)2Br, 46 mg of CsI, 25 mg of CsBr, 428 mg of PbI2 and 209 mg of PbBr2 were added to 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO was 3:1), stirred at 600 rpm on a magnetic stirrer for 2 h, and filtered to obtain the first perovskite precursor solution. 100 μL of the above-mentioned first perovskite precursor solution was spin-coated onto the hole transport layer prepared in step S20 (spin-coated at a spin-coating speed of 2000 rpm for 10 s, and then spin-coated at a spin-coating speed of 4000 rpm for 30 s), and then 250 μL of chlorobenzene was dropped onto the spin-coated first perovskite precursor solution, and then the above-mentioned first perovskite precursor solution was spin-coated again, and then transferred to a hot stage for annealing at 100°C for 10 min to form a first perovskite layer.
[0502] S80 used the anti-solvent method to prepare the second perovskite layer: 216 mg of CH(NH2)2I, 85 mg of CH3NH2I, 414 mg of PbI2, 335 mg of SnI2, and 0.3 mg of MeO-4PACz were added to 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF to DMSO was 3:1), stirred at 600 rpm on a magnetic stirrer for 2 h, and filtered to obtain the second perovskite precursor solution. liquid; spin-coat 100 μL of the above-mentioned second perovskite precursor solution onto the PEDOT:PSS film layer prepared in step S70 (spin-coat at a spin-coating speed of 1000 rpm for 10 s, and then spin-coat at a spin-coating speed of 4000 rpm for 30 s), then drop 300 μL of ethyl acetate onto the spin-coated second perovskite precursor solution, then spin-coat the above-mentioned second perovskite precursor solution again, and then transfer to a hot stage and anneal at 100° C. for 10 min to form a second perovskite layer.
[0503] Comparative Example 2. Preparation of the first perovskite layer and the second perovskite layer by anti-solvent method
[0504] Comparative Example 2 adopts a method substantially the same as Example 2, except that the method for preparing the first perovskite layer in S30 and the method for preparing the second perovskite layer in S80 are different, both of which adopt the anti-solvent method.
[0505] S20 used the anti-solvent method to prepare the first perovskite layer: 123 mg of CH(NH2)2I, 59 mg of CH(NH2)2Br, 46 mg of CsI, 25 mg of CsBr, 428 mg of PbI2 and 209 mg of PbBr2 were added to 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO was 3:1), stirred at 600 rpm on a magnetic stirrer for 2 h, and filtered to obtain the first perovskite precursor solution. 100 μL of the above-mentioned first perovskite precursor solution was spin-coated onto the hole transport layer prepared in step S20 (spin-coated at a spin-coating speed of 2000 rpm for 10 s, and then spin-coated at a spin-coating speed of 4000 rpm for 30 s), and then 250 μL of chlorobenzene was dropped onto the spin-coated first perovskite precursor solution, and then the above-mentioned first perovskite precursor solution was spin-coated again, and then transferred to a hot stage for annealing at 100°C for 10 min to form a first perovskite layer.
[0506] S80 used the anti-solvent method to prepare the second perovskite layer: 216 mg of CH(NH2)2I, 85 mg of CH3NH2I, 414 mg of PbI2, 335 mg of SnI2, and 0.3 mg of MeO-4PACz were added to 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF to DMSO was 3:1), stirred at 600 rpm on a magnetic stirrer for 2 h, and filtered to obtain the second perovskite precursor solution. liquid; spin-coat 100 μL of the above-mentioned second perovskite precursor solution onto the PEDOT:PSS film layer prepared in step S70 (spin-coat at a spin-coating speed of 1000 rpm for 10 s, and then spin-coat at a spin-coating speed of 4000 rpm for 30 s), then drop 300 μL of ethyl acetate onto the spin-coated second perovskite precursor solution, then spin-coat the above-mentioned second perovskite precursor solution again, and then transfer to a hot stage and anneal at 100° C. for 10 min to form a second perovskite layer.
[0507] Comparative Example 3. Preparation of the first perovskite layer and the second perovskite layer by anti-solvent method
[0508] Comparative Example 3 adopts a method substantially the same as that of Comparative Example 2, and both adopt an anti-solvent method to prepare the first perovskite layer and the second perovskite layer. The difference is that the first perovskite precursor solution used in S30 to prepare the first perovskite layer is the same, and the corresponding perovskite metal halide is FAPbI 3-y Br y , y=1.2.
[0509] Comparative Examples 4-5 use a method substantially the same as that of Example 1, except that: the first perovskite precursor solution used in preparing the first perovskite layer is the same, and the corresponding perovskite metal halide CsaFA 1-a PbI 3-y Br y In (a=0.4), y is 0 and 3 respectively. Please refer to Table 1.
[0510] Comparative Examples 6-7 use a method substantially the same as Example 1, except that the first perovskite layer and the second perovskite layer are prepared by different methods, both of which are evaporation methods. See Table 1.
[0511] Among them, the step of preparing a wide band gap in step S30 is: 154 mg of CH(NH2)2I, 74 mg of CH(NH2)2Br, 428 mg of PbI2 and 209 mg of PbBr2 are added to 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 3:1), stirred at 600 rpm on a magnetic stirrer for 2 hours, filtered, and the first perovskite precursor solution is prepared. 100 μL of the above first perovskite precursor solution is spin-coated on the hole transport layer prepared in step S20 (spin-coated at a spin-coating speed of 2000 rpm for 10 seconds, and then spin-coated at a spin-coating speed of 4000 rpm for 30 seconds), and then 250 μL of chlorobenzene is added dropwise to the spin-coated perovskite precursor solution, followed by spin-coating the above perovskite precursor solution, and then transferred to a hot stage for annealing at 100°C for 10 minutes to form a first perovskite layer.
[0512] Among them, the step of preparing the narrow band gap in step S80 is: adding 216 mg of CH(NH2)2I, 85 mg of CH3NH2I, 414 mg of PbI2, 335 mg of SnI2, and 0.3 mg of MeO-4PACz to 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 3:1), stirring at 600 rpm on a magnetic stirrer for 2 h, filtering, and obtaining the second perovskite Precursor solution; spin coat 100 μL of the above second perovskite precursor solution onto the PEDOT:PSS film layer prepared in step S70 (spin coat at a spin coating speed of 1000 rpm for 10 s, and then spin coat at a spin coating speed of 4000 rpm for 30 s), then drop 300 μL of ethyl acetate onto the spin-coated perovskite precursor solution, and then spin coat the above perovskite precursor solution again, and then transfer to a hot stage and anneal at 100 ° C for 10 min to form a second perovskite layer.
[0513] Please refer to Table 1.
[0514] Table 1.
[0515]
[0516]
[0517] Test Method
[0518] 1. Morphology and structure test
[0519] For the sample to be tested, it is fixed on the sample holder with conductive tape for testing. Scanning Electron Microscope (SEM) is an experimental observation method between transmission electron microscope and optical microscope. This is an electronic optical instrument that uses an electron beam to scan the surface of the observed sample, and then collects a series of electronic information generated by the interaction between the electron beam and the sample, converts, amplifies and digitally processes it to form an image. It has a large depth of field, a large field of view, and a good three-dimensional imaging effect, and can effectively analyze the surface morphology of the sample. The magnification can be changed by changing the scanning amplitude of the electron beam on the sample surface, and the test sample can be magnified and observed by about 20 times to 200,000 times. The crystallization of the perovskite sample (such as grain size, grain thickness, "whether there are through-type grains with a lateral size ≥ 400nm", etc.) and morphological characteristics can be observed through SEM.
[0520] SEM test object: Based on the first electrode (transparent electrode), it can be a component sample in which the first perovskite layer has been deposited on the hole transport layer but the second carrier transport layer has not yet been deposited. It can be tested and analyzed in both the vertical and horizontal directions; component samples in which the second perovskite layer has been deposited.
[0521] (1) The observation surface is the exposed surface of the first perovskite layer, or the transparent surface of the first electrode.
[0522] (2) Use a glass cutter to cut a 1×0.5 cm 2 The component samples were glued onto the SEM sample preparation table with the longitudinal section facing upwards, and the crystal quality and grain thickness were observed using SEM.
[0523] According to the SEM images of the longitudinal cross-section, combined with analysis software such as Image-J, the dimensions of the concave grooves and convex ridges, the area ratio of the through-type grains with a lateral dimension of ≥400nm in the longitudinal cross-section, and other related information can be obtained. The dimensions of the concave grooves include the width, average width, length, aspect ratio, half-height width, average half-height width, depth, average depth, depth-to-width ratio, average depth-to-width ratio, average spacing and other dimensional parameters of the concave grooves. The dimensions of the convex ridges include the width, average width, length, aspect ratio, half-height width, average half-height width, height, average height, aspect ratio, average height-to-width ratio, average spacing and other dimensional parameters of the convex ridges. The average of the above parameters is collected from at least three areas.
[0524] The depth of the concave groove and the height of the convex ridge are basically consistent in average value.
[0525] 2. Analysis of the surface roughness and structural dimensions of the first perovskite layer.
[0526] The surface roughness and groove structure of the first perovskite layer were tested using a step profiler (probe profiler).
[0527] Sample to be tested: The component in which the first perovskite layer has been deposited on the first carrier transport layer and the second carrier transport layer has not been deposited is used as the sample to be tested (step S30 has been completed and step S40 has not yet been performed), and the lateral surface of one side of the perovskite layer is used as the test surface. The test results can be found in Table 2.
[0528] Test conditions: The probe directly contacts the surface to record the profile change, and the two-dimensional profile change and calculated line roughness can be obtained.
[0529] The test is conducted in a contact-motion mode: when the stylus lightly slides along the surface to be tested, the stylus moves up and down along the tiny peaks and valleys on the surface while sliding. The motion trajectory of the stylus reflects the surface profile.
[0530] Test results and analysis methods: The topography curve of the surface (which can be called the surface roughness curve) can be obtained. The "valley" in the curve corresponds to the concave groove, and the area between the two nearest peaks with a fluctuation depth ≥100nm is regarded as a "valley"; the "peak" in the curve corresponds to the convex ridge, and the area between the two nearest valleys with a fluctuation height ≥100nm is regarded as a "peak". The surface roughness of the surface to be tested can be obtained by counting the "valley depth" or "peak height" in the surface roughness curve; further, the width, average width, length, aspect ratio, half-height width, average half-height width, depth, average depth, aspect ratio, average aspect ratio, average interval and other dimensional parameters of the concave groove can be obtained by analysis. Similarly, the width, average width, length, aspect ratio, half-height width, average half-height width, height, average height, aspect ratio, average aspect ratio, average interval and other dimensional parameters of the convex ridge can be obtained by analysis. In addition, these dimensional parameters of the concave grooves and convex ridges can also be obtained by observing and analyzing the SEM images of the longitudinal cross-section at a certain magnification, such as magnifications of 20K, 30K, and 40K.
[0531] 3. Optical microscope observation
[0532] Sample to be tested: a thin film component in which the first perovskite layer has been deposited on the first carrier transport layer but the electron transport layer has not been deposited (step S30 has been completed and step S40 has not yet been performed), and the exposed surface of the first perovskite layer is used as the test surface. The lateral dimension of the component is recorded as A2.
[0533] Instrument: Optical microscope (Keyence VHX-S650E), place the test surface directly under the light beam, adjust the focus and observe.
[0534] Sample to be tested: a thin film component in which the first perovskite layer has been deposited on the first carrier transport layer and the electron transport layer has not been deposited (step S30 has been completed and step S40 has not yet been performed), and the exposed surface of the first perovskite layer is used as the test surface.
[0535] Test analysis method:
[0536] Select at least 960000μm 2 Statistical analysis was performed within the area.
[0537] (1) A non-smooth surface morphology image of the first perovskite can be obtained. The area enclosed by the outline of the concave groove in the image is recorded as A1, and the "percentage of the sum of the projection areas of the concave grooves along the longitudinal direction relative to the projection area of the non-smooth surface along the longitudinal direction (recorded as R1)" = A1 / A2×100%.
[0538] (2) The distances between multiple adjacent concave grooves can also be measured based on the center line analysis of the concave groove width, and the average value can be taken to obtain the average spacing of the concave grooves.
[0539] The average spacing between the convex ridges and the average spacing between the concave grooves are basically consistent in value.
[0540] 4. Laminated solar cell performance test
[0541] The stacked solar cell to be tested is connected to a dedicated capacitor and used as a variable load. In the process of charging the capacitor by the stacked solar cell, current and voltage sampling is performed, and the corresponding current and voltage data are recorded and plotted into a volt-ampere characteristic curve (IV curve). The electrical performance parameters are calculated to obtain the test values of open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and photoelectric conversion efficiency (PCE).
[0542] Test method: Use a solar simulator to test according to the national standard IEC61215. Use a crystalline silicon solar cell to calibrate the light intensity to reach the intensity of one sun, AM 1.5. Connect the battery to a digital source meter and test the photoelectric conversion efficiency PCE under illumination.
[0543] In the atmospheric environment, the AM1.5G standard light source is used as the sunlight simulation light source, and a four-channel digital source meter (Keithley 2440) is used to measure the volt-ampere characteristic curve of the battery under the irradiation of the light source to obtain the open circuit voltage Voc, short circuit current density Jsc, and fill factor FF (Fill Factor) of the battery, thereby calculating the photoelectric conversion efficiency PCE of the stacked solar cell.
[0544] The photoelectric conversion efficiency is calculated as follows: PCE = Pout / Popt
[0545] =Voc×Jsc×(Vmpp×Jmpp) / (Voc×Jsc)
[0546] =Voc×Jsc×FF
[0547] Among them, Pout, Popt, Vmpp, and Jmpp are the battery operating output power, incident light power, battery maximum power point voltage, and maximum power point current, respectively.
[0548] Test analysis results
[0549] According to the test results, the first perovskite layer prepared in Examples 1-9 forms a non-smooth surface on the side away from the first electrode, and the non-smooth surface includes staggered concave grooves and convex ridges, convex ridges are formed between adjacent concave grooves, and concave grooves are formed between adjacent convex ridges. The laminated solar cell further prepared has a "concave-convex" interface formed by staggered arrangement of concave grooves and convex ridges at the first interface.
[0550] In Comparative Examples 1-7, the first perovskite layer in Comparative Examples 1-3 is prepared by a traditional anti-solvent method, the two perovskite layers in Comparative Examples 6-7 are prepared by an evaporation process, and Comparative Examples 4-5 include only one halogen, I and Br. In Comparative Examples 1-7, basically no non-smooth surface is formed at the first interface, which can be regarded as a relatively flat surface with basically no concave grooves or convex ridge structures.
[0551] Figure 1 This is an optical microscope observation image of the non-smooth surface of the first perovskite layer prepared by the vacuum flash evaporation method in Example 1; Figure 2 This is an optical microscope observation image of the non-smooth surface of the first perovskite layer prepared by the vacuum flash evaporation method in Example 2; Figure 3 This is an optical microscope observation picture observed from the glass substrate side in Example 1, in which a transparent electrode, a hole transport layer and a first perovskite layer are arranged in sequence.
[0552] Figure 1 In the figure, obvious grooves can be observed, and ridges are formed between the grooves. The overall distribution of the grooves and ridges on the surface of the first perovskite layer is relatively uniform, and the lateral size combination of the grooves and ridges is relatively matched, presenting a wrinkled morphology as a whole.
[0553] See also Figure 1 There are concave grooves with an extension length of ≥50 μm and convex ridges with an extension length of ≥50 μm on the non-smooth surface of the first perovskite layer.
[0554] from Figure 1 It can also be seen that the aspect ratio of most ridges is greater than 1, and can meet a variety of aspect ratio ranges of ridges, including but not limited to ridges meeting the following aspect ratios: ≥2, ≥3, ≥5, greater than 1 and less than or equal to 20, 2-10, 5-10, etc.
[0555] from Figure 1It can also be seen that the aspect ratio of most of the concave grooves is greater than 1; the illustrated area can meet the aspect ratio ranges of various concave grooves, including but not limited to concave grooves meeting the following aspect ratios: ≥5, ≥10, ≥15, greater than 1 and less than or equal to 20, 2-20, 5-20, 10-20, etc.
[0556] from Figure 1 It can also be seen that some of the concave grooves have corners in their extension direction. Some of the concave grooves have non-straight lines in their extension direction. Some of the adjacent concave grooves have intersection nodes, that is, some of the adjacent concave grooves are connected through the intersection nodes.
[0557] from Figure 1 It can also be seen that there are corners in the extension direction of some ridges. There are non-straight lines in the extension direction of some ridges. There are intersection nodes between some adjacent ridges, that is, some adjacent ridges are connected through the intersection nodes.
[0558] Figure 8 This is an optical microscope observation picture of the all-perovskite stacked solar cell in Comparative Example 1 from the glass substrate side, wherein a transparent electrode is provided on the surface of the glass substrate close to the carrier recombination layer. Fig. 9 This is a scanning electron microscope (SEM) image of the longitudinal cross section of the stacked solar cell prepared by the anti-solvent method in Comparative Example 1.
[0559] Based on the direct observation of the non-smooth surface of the first perovskite layer using an optical microscope, the transverse and longitudinal cross-sections of the SEM (see Figure 1 , Figure 4-6 ) and the surface roughness test and analysis results of the non-smooth surface, the morphology and size parameters of the concave grooves and convex ridges can be obtained, including but not limited to: the width, average width, length, aspect ratio, half-height width, average half-height width, depth, average depth, aspect ratio, average depth-to-width ratio, average spacing and other size parameters of the concave grooves, such as the width, average width, length, aspect ratio, half-height width, average half-height width, height, average height, aspect ratio, average aspect ratio, average spacing and other size parameters of the convex ridges, the percentage of the sum of the projected areas of the concave grooves along the longitudinal direction to the projected area of the non-smooth surface along the longitudinal direction, the ratio of the half-height width of the convex ridge to the half-height width of the adjacent concave grooves, the ratio of the average half-height width of the convex ridge to the average half-height width of the concave grooves, the ratio of the sum of the areas of the half-height cross-sections of the convex ridges to the sum of the areas of the half-height cross-sections of the concave grooves, the percentage of the sum of the projected areas of the concave grooves along the longitudinal direction to the projected area of the non-smooth surface along the longitudinal direction, etc. The average depth of the concave grooves, the average height of the convex ridges and the surface roughness in the test area are substantially equal in value; the average interval of the convex ridges and the average interval of the concave grooves in the test area are substantially consistent in value.
[0560] In Examples 1-9, the average width of the concave grooves at the non-smooth surface of the first perovskite layer satisfies the two ranges of 0.3μm to 1μm and 0.5μm to 1μm at the same time, the average half-height width satisfies the two ranges of 0.2μm to 0.7μm and 0.3μm to 0.55μm at the same time, the average depth satisfies the two ranges of 100nm to 500nm and 100nm to 250nm at the same time, and the average aspect ratio satisfies the three ranges of 0.03 to 0.5, 0.2 to 0.5 and 0.25 to 0.3 at the same time. As an example, the average width of Example 1 is about 0.8μm, the average half-height width is about 0.4μm, the average depth is about 200nm, and the average aspect ratio is about 0.28. The average width, average half-height width, average depth and average aspect ratio in each of Examples 1-9 are relatively close. In Examples 1-9, the ratio of the sum of the areas of the half-height cross sections of the ridges to the sum of the areas of the half-height cross sections of the concave grooves satisfies both 1 to 36 and 10 to 30. In each of Examples 1-9, the morphologies of the interfaces formed by the different structural layers between the first perovskite layer and the second perovskite layer are substantially matched. The ridges and concave grooves in most non-smooth regions satisfy that the half-height width of the ridges is greater than the half-height width of the adjacent concave grooves. According to the test and analysis results, on the non-smooth surface of the first perovskite layer, most of the concave grooves have a longitudinal cross-sectional shape that is wide at the top and narrow at the bottom, the opening width of some concave grooves is greater than the bottom width, and the opening width of some concave grooves> half-height width> bottom width; in terms of the proportion of the projection area of the concave grooves along the longitudinal direction, in some non-smooth areas, the concave grooves with an opening width greater than the bottom width meet ≥50%, and in some non-smooth areas, the concave grooves with an opening width greater than the bottom width meet ≥80%; in terms of the proportion of the projection area of the concave grooves along the longitudinal direction, in some non-smooth areas, the concave grooves with an opening width> half-height width> bottom width meet ≥50%, and in some non-smooth areas, the concave grooves with an opening width> half-height width> bottom width meet ≥80%. According to the test and analysis results, on the non-smooth surface of the first perovskite layer, most of the convex ridges have a longitudinal cross-sectional shape that is narrow at the top and wide at the bottom, and the bottom width of the convex ridges is greater than the top width; in terms of the proportion of the projection area of the convex ridges along the longitudinal direction, in some non-smooth areas, the convex ridges with a bottom width greater than the top width meet ≥50%, and in some non-smooth areas, the convex ridges with a bottom width greater than the top width meet ≥80%. The half-height width of at least a portion of the ridges is within the following two ranges: 1 μm to 2.5 μm and 1.5 μm to 2 μm. The half-height width of at least a portion of the concave grooves is within the following two ranges: ≤1 μm and 0.2 μm to 0.7 μm. The ratio of the average half-height width of the ridges to the average half-height width of the grooves in the partial test area satisfies both the ranges of 1 to 6 and 4 to 5, and the ratio of the sum of the areas of the half-height cross-sections to the sum of the areas of the half-height cross-sections of the concave grooves satisfies both the ranges of 1 to 36 and 10 to 30.
[0561] In each case, there are some test areas that satisfy: the maximum width of the ridge within the extended length does not exceed 30% relative to the average width of the ridge; there are also some test areas that satisfy: the maximum width of the ridge within the extended length does not exceed 30% relative to the average width of the ridge. Figure 1 .
[0562] In Examples 1-9, in most test areas, the average spacing of the concave grooves satisfies 1 μm to 20 μm; in some test areas, the average spacing of the concave grooves satisfies 10 μm to 20 μm. In the test area, the average spacing of the ridges is basically consistent with the average spacing of the concave grooves. Figure 1 .
[0563] In Examples 1-9, there are two adjacent concave grooves in a certain extension length region that satisfy the angle between the extension directions ≤15° or ≤30°, including but not limited to in at least one of an extension length region of at least 30μm, at least 50μm and at least 80μm; there are also two adjacent convex ridges in a certain extension length region that satisfy the angle between the extension directions ≤15° or ≤30°, including but not limited to in at least one of an extension length region of at least 30μm, at least 50μm and at least 80μm. In some embodiments of Examples 1-9, there are two adjacent concave grooves in an extension length region of at least 80μm that satisfy the angle between the extension directions ≤30°. In some embodiments of Examples 1-9, there are two adjacent convex ridges in an extension length region of at least 80μm that satisfy the angle between the extension directions ≤30°. See. Figure 1 .
[0564] Figure 4 for Figure 1 A scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell prepared by the vacuum flash evaporation method in the illustrated embodiment. Figure 5 for Figure 2 A scanning electron microscope (SEM) image of a longitudinal cross section of a stacked solar cell prepared by the vacuum flash evaporation method in Example 2 is shown. Figure 6 for Figure 5 The lateral cross-sectional scanning electron microscope (SEM) image of the wide bandgap perovskite layer prepared by the vacuum flash evaporation method in Example 2 is shown.
[0565] according to Figure 4 and Figure 5 In the laminated solar cells prepared by the vacuum flash evaporation method in Example 1 and Example 2, the perovskite crystal quality of the first perovskite layer and the second perovskite layer is high, the average size of the perovskite grains in the perovskite layer is large, and there are few defects. The longitudinal cross-section of the perovskite layer has few cracks, forming a through-type grain that is integrated in the longitudinal direction. The lateral size of some through-type grains is ≥400nm. The lateral size of some through-type grains is ≥500nm. Figure 5 In the embodiment, the area percentage of through-type grains with a lateral size of ≥400 nm relative to the longitudinal cross section is greater than 80%. Figure 4 In the embodiment, the area percentage of through-type grains with a lateral size of ≥400 nm relative to the longitudinal cross section is greater than 80%.
[0566] In Examples 1-9, the average lateral size of the through-type grains satisfies 300nm to 2μm. The average lateral size of the through-type grains in some of the embodiments satisfies 400nm to 1μm. The average lateral size of the through-type grains in some of the embodiments satisfies 500nm to 800nm. In some of the embodiments, within a width region of at least 10μm of the longitudinal cross section of the first perovskite layer, the area percentage of the through-type grains with a lateral size ≥400nm relative to the longitudinal cross section satisfies ≥90%.
[0567] according to Fig. 9 In the tandem solar cell prepared by the anti-solvent method in Comparative Example 1, the average size of the perovskite grains in the first perovskite layer and the second perovskite layer is relatively small, and the perovskite layer has many defects. Many broken crystals are observed in the longitudinal cross section, and there are basically no through-type grains, that is, most of the grains are difficult to integrate in the longitudinal direction, which easily hinders the carrier transmission process.
[0568] Table 2. Non-smooth surface of the first perovskite layer (the surface of the first perovskite layer facing away from the first electrode)
[0569]
[0570]
[0571] In Examples 1-9, the average depth of the concave grooves, the average height of the convex ridges and the surface roughness in the test area are substantially equal in value; in the test area, the average spacing of the convex ridges is substantially consistent in value with the average spacing of the concave grooves.
[0572] Table 3.
[0573]
[0574] In Table 3, R1 represents the percentage of the sum of the projected areas of the concave grooves along the longitudinal direction relative to the projected area of the non-smooth surface along the longitudinal direction.
[0575] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.
[0576] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0577] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. The above-mentioned embodiments only express several embodiments of the present application, and the description thereof is relatively detailed, but it cannot be understood as a limitation on the scope of the patent. In addition, without departing from the scope of the subject matter of the present application, various deformations that can be thought of by those skilled in the art and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A perovskite-based tandem solar cell, characterized in that: The stacked solar cell comprises a first perovskite subcell, a carrier recombination layer, and a second perovskite subcell which are stacked in sequence, wherein the first perovskite subcell comprises a first perovskite layer, and the second perovskite subcell comprises a second perovskite layer; the band gap of the first perovskite layer is different from the band gap of the second perovskite layer; Wherein, the thickness direction of the first perovskite layer is recorded as the longitudinal direction; The surface of the first perovskite layer on one side close to the carrier recombination layer is a non-smooth surface, the non-smooth surface is provided with concave grooves, and convex edges are formed between at least a portion of adjacent concave grooves; The stacked solar cell meets at least one of the following characteristics: At least a portion of the concave grooves have different widths at at least a portion of the depth positions; At least a portion of the ridges have different widths at at least a portion of their heights.
2. The tandem solar cell according to claim 1, characterized in that: The morphologies of interfaces formed by different structural layers between the first perovskite layer and the second perovskite layer are substantially matched.
3. The tandem solar cell according to claim 1 or 2, characterized in that: Meet one or more of the following characteristics: The width of at least a portion of the ridges is 0.5 μm to 4 μm, and can be further 2 μm to 3.5 μm; The half-height width of at least a portion of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm; The height of at least a portion of the ridges is greater than or equal to 100 nm, and may further be 100 nm to 250 nm; In at least a portion of the non-smooth surface, the average width of the ridges is 0.5 μm to 4 μm, and may be further 2 μm to 3.5 μm; In at least a portion of the non-smooth surface, the average half-height width of the ridges is 1 μm to 2.5 μm, and can be 1.5 μm to 2 μm; In at least a portion of the non-smooth surface, the average height of the ridges is 100 nm to 500 nm, and may be 100 nm to 250 nm; Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is greater than or equal to 0.1 mm 2 , further optional to be greater than or equal to 0.6mm 2 .
4. The tandem solar cell according to any one of claims 1 to 3, characterized in that: Meet one or more of the following characteristics: The width of at least a portion of the concave grooves is less than or equal to 1.2 μm, and may be 0.5 μm to 1 μm; The half-height width of at least a portion of the concave grooves is less than or equal to 1 μm, and can be optionally 0.2 μm to 0.7 μm; The depth of at least a portion of the concave grooves is greater than or equal to 100 nm, and can further be 100 nm to 250 nm; The aspect ratio of at least a portion of the concave grooves is 0.03 to 0.5, and can be further 0.25 to 0.35; In at least a portion of the non-smooth surface, the average width of the concave groove is 0.3 μm to 1 μm, and can be 0.5 μm to 1 μm; In at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.2 μm to 0.7 μm, and can be 0.3 μm to 0.55 μm; In at least a portion of the non-smooth surface, the average depth of the concave groove is 100nm to 500nm, and can be 100nm to 250nm; In at least a portion of the non-smooth surface, the average depth-to-width ratio of the concave groove is 0.03 to 0.5, and can be further 0.25 to 0.35; Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is greater than or equal to 0.1 mm 2 , further optional to be greater than or equal to 0.6mm 2 .
5. The tandem solar cell according to any one of claims 1 to 4, characterized in that: Meet one or more of the following characteristics: In at least a portion of the non-smooth surface, the average spacing of the ridges is 1 μm to 20 μm, and can be 10 μm to 20 μm; In at least a portion of the non-smooth surface, the average spacing of the concave grooves is 1 μm to 20 μm, and can be 10 μm to 20 μm; The half-height width of at least a portion of the convex ridges is greater than the half-height width of the adjacent concave grooves; In at least a portion of the non-smooth surface, the ratio of the average half-height width of the convex ridges to the average half-height width of the concave grooves is 1 to 6, and can further be 4 to 5; In at least a portion of the non-smooth surface, the ratio of the sum of the half-height cross-section areas of the ridges to the sum of the half-height cross-section areas of the concave grooves is 1 to 36, and may further be 10 to 30; In at least a portion of the non-smooth surface, the percentage of the sum of the projection areas of the concave grooves along the longitudinal direction relative to the projection area of the non-smooth surface along the longitudinal direction is 5% to 95%, and can further be 10% to 50%; Optionally, the projection area of at least a portion of the non-smooth surface along the longitudinal direction is greater than or equal to 0.1 mm 2 , further optional to be greater than or equal to 0.6mm 2 .
6. The tandem solar cell according to any one of claims 1 to 5, characterized in that: The opening width of at least a portion of the concave grooves is greater than the bottom width; Optionally, based on the proportion of the projection area of the concave grooves along the longitudinal direction, at least 50% of the opening widths of the concave grooves are greater than the bottom widths; Further optionally, at least 80% of the concave grooves have an opening width greater than a bottom width; Optionally, based on the proportion of the projected area of the concave groove along the longitudinal direction, the opening width of at least a portion of the concave grooves is greater than the half-height width and the bottom width; further optionally, at least 50% of the concave grooves have an opening width greater than the half-height width and the bottom width; further optionally, at least 80% of the concave grooves have an opening width greater than the half-height width and the bottom width.
7. The tandem solar cell according to any one of claims 1 to 6, characterized in that: The bottom width of at least a portion of the ridges is greater than the top width; Optionally, based on the proportion of the projection area of the ridges along the longitudinal direction, at least 50% of the ridges have a bottom width greater than a top width; Further optionally, at least 80% of the ridges have a bottom width greater than a top width; Optionally, based on the proportion of the projected area of the ridges along the longitudinal direction, at least a portion of the ridges have a bottom width > half-height width > top width; further optionally, at least 50% of the ridges have a bottom width > half-height width > top width; further optionally, at least 80% of the ridges have a bottom width > half-height width > top width.
8. The tandem solar cell according to any one of claims 1 to 7, characterized in that: Meet one or more of the following characteristics: At least a portion of the concave grooves have corners in their extending directions; At least a portion of the concave grooves have a non-linear extension direction; At least a portion of the concave grooves have intersection nodes; At least a portion of the ridges have corners in their extension direction; At least a portion of the ridges extending in a direction in which at least a portion of the ridges extend is non-linear; At least a portion of the convex edges have intersection nodes; The maximum width of at least a portion of the concave grooves within the extended length deviates by no more than 30% from the average width of the concave grooves; The maximum width of at least a portion of the ridges within the extended length deviates by no more than 30% from the average width of the ridges; The extension length of at least a portion of the concave grooves is greater than or equal to 50 μm; The extension length of at least a portion of the ridges is greater than or equal to 50 μm; The aspect ratio of at least a portion of the concave grooves is greater than or equal to 2. Optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 5. The aspect ratio of at least a portion of the concave grooves is 1 to 10, and can be 5 to 10; The aspect ratio of at least a portion of the ridges is greater than or equal to 2. Optionally, the aspect ratio of at least a portion of the ridges is greater than or equal to 5. The aspect ratio of at least a portion of the ridges is 1-20, and can be optionally 10-20.
9. The tandem solar cell according to any one of claims 1 to 8, characterized in that: Meet one or more of the following characteristics: The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° in an extension length region of at least 30 μm; The angle between the extension directions of at least a portion of two adjacent convex ridges satisfies ≤30° in an extension length region of at least 30 μm.
10. The tandem solar cell according to claim 9, characterized in that: Meet one or more of the following characteristics: The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 30 μm; optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 50 μm; further optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤15° over an extension length of at least 80 μm; The angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° over an extension length of at least 50 μm; optionally, the angle between the extension directions of at least a portion of two adjacent concave grooves satisfies ≤30° over an extension length of at least 80 μm; The angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 30 μm; optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 50 μm; further optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤15° over an extension length of at least 80 μm; The angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤30° over an extension length of at least 50 μm; optionally, the angle between the extension directions of at least a portion of two adjacent ridges satisfies ≤30° over an extension length of at least 80 μm.
11. The tandem solar cell according to any one of claims 1 to 10, characterized in that: The band gap of the first perovskite layer is greater than the band gap of the second perovskite layer; Optionally, the band gap of the first perovskite layer is 1.2 eV to 2.4 eV, and optionally 1.6 eV to 2.3 eV; the band gap of the second perovskite layer is 1.0 eV to 1.4 eV.
12. The tandem solar cell according to any one of claims 1 to 11, characterized in that: The first perovskite layer includes a first perovskite metal halide, and the halogen in the first perovskite metal halide includes bromine and iodine; optionally, the halogen in the first perovskite metal halide is a combination of bromine and iodine; Optionally, the second perovskite layer includes a second perovskite-type metal halide, and the halogen in the second perovskite-type metal halide includes iodine; further optionally, the halogen in the second perovskite-type metal halide is iodine.
13. The tandem solar cell according to claim 12, characterized in that: The atomic molar ratio of bromine element to iodine element in the first perovskite metal halide is (3 - y):y, where 0 < y ≤ 2; optionally, 1 ≤ y ≤ 2.
14. The tandem solar cell according to any one of claims 1 to 13, characterized in that: At least a part of the perovskite grains in the first perovskite layer are through - type grains, and both ends of the through - type grains along the longitudinal direction are located on the two side surfaces of the first perovskite layer respectively.
15. The tandem solar cell according to claim 14, characterized in that: The lateral size of at least a part of the through - type grains is greater than or equal to 500 nm; wherein, the lateral direction is orthogonal to the longitudinal direction, and the lateral size of the through - type grains represents the maximum size among the anisotropic sizes of the grains in the lateral cross - section. Optionally, the lateral size of at least a part of the through - type grains is greater than or equal to 400 nm, and can be greater than or equal to 500 nm. Optionally, the average lateral size of the through - type grains is 300 nm - 2 μm, can be 400 nm - 1 μm, and further can be 500 nm - 800 nm.
16. The tandem solar cell according to claim 14 or 15, characterized in that: On the longitudinal section of the first perovskite layer, the area percentage of the through - type grains relative to the longitudinal section is greater than or equal to 80%, and can be greater than or equal to 90%.
17. The tandem solar cell according to any one of claims 14 to 16, characterized in that: In at least a part of the width region of the longitudinal section of the first perovskite layer, the area percentage of the through - type grains with a lateral size greater than or equal to 400 nm relative to the longitudinal section is greater than or equal to 80%, and can be greater than or equal to 90%. Optionally, at least a part of the width region of the longitudinal section of the first perovskite layer corresponds to a width region of at least 10 μm.
18. The tandem solar cell according to any one of claims 1 to 17, characterized in that: Satisfy one or more of the following characteristics: Both the first carrier transport layer and the third carrier transport layer are electron transport layers, and both the second carrier transport layer and the fourth carrier transport layer are hole transport layers, or both the first carrier transport layer and the third carrier transport layer are hole transport layers, and both the second carrier transport layer and the fourth carrier transport layer are electron transport layers. The tandem solar cell further includes a first electrode and a second electrode. The first electrode is located on the side of the first perovskite sub - cell away from the carrier recombination layer, and the second electrode is located on the side of the second perovskite sub - cell away from the carrier recombination layer; the first electrode is a transparent electrode. At least one side of the first carrier transport layer includes a hetero - carrier blocking layer. At least one side of the second carrier transport layer includes a hetero - carrier blocking layer. At least one side of the third carrier transport layer includes a hetero - carrier blocking layer. At least one side of the fourth carrier transport layer includes a hetero - carrier blocking layer.
19. The tandem solar cell according to any one of claims 1 to 18, characterized in that: The first perovskite sub - cell and the second perovskite sub - cell form a two - terminal integrated structure.
20. The tandem solar cell according to any one of claims 1 to 19, characterized in that: The described tandem solar cell is a two - terminal tandem solar cell.
21. The tandem solar cell according to any one of claims 1 to 20, characterized in that: The described tandem solar cell is an all - perovskite tandem solar cell.
22. The method for preparing a perovskite-based tandem solar cell according to any one of claims 1 to 21, characterized in that: Including the following steps: sequentially stack a first carrier transport layer, a first perovskite layer, a second carrier transport layer, a carrier recombination layer, a third carrier transport layer, a second perovskite layer, a fourth carrier transport layer, and a second electrode on one side surface of the first electrode to prepare the perovskite - based tandem solar cell. The method of stacking the first perovskite layer on the side of the first carrier transport layer facing away from the first electrode comprises the following steps: Applying the precursor solution I of the first perovskite layer to the surface of the first carrier transport layer on the side away from the first electrode to form a coating layer I; The coating layer I is subjected to vacuum flash evaporation treatment and annealing treatment to form the first perovskite layer, and the non-smooth surface is formed on a side of the first perovskite layer away from the first electrode.
23. The preparation method according to claim 22, characterized in that: The preparation method meets one or more of the following characteristics: The vacuum flash evaporation treatment is carried out under negative pressure conditions, and the negative pressure condition is less than or equal to 100 Pa, and can be selected from 50 Pa to 100 Pa; The temperature for the vacuum flash treatment is -10°C to 100°C, optionally 0°C to 30°C, and further optionally 20°C to 30°C; The duration of the vacuum flash treatment is 10s to 100s, optionally 10s to 30s, and further optionally 15s to 25s; The annealing treatment is performed by a hot stage, optionally, a 30°C to 200°C hot stage, further optionally, a 90°C to 110°C hot stage, and further optionally, a 98°C to 102°C hot stage; The annealing time of the annealing treatment is 30s to 60min, optionally 5min to 20min, and further optionally 14min to 16min.
24. The preparation method according to claim 22 or 23, characterized in that: The step of coating the precursor solution I of the first perovskite layer onto the surface of the first carrier transport layer on the side away from the first electrode comprises: Spin coating a portion of the precursor solution I onto a surface of the first carrier transport layer that is away from the first electrode at a first rotation speed; Accelerating the rotation speed from the first rotation speed to a second rotation speed, and continuing to spin-coat another portion of the precursor liquid I at the second rotation speed; Wherein, the second rotation speed is greater than the first rotation speed.
25. The preparation method according to claim 24, characterized in that: Meet one or more of the following characteristics: The first rotation speed is 1000 rpm to 6000 rpm, and can be optionally 1000 rpm to 2000 rpm; the spin coating is performed at the first rotation speed for 8 s to 12 s; In the step of accelerating the rotation speed from the first rotation speed to the second rotation speed, the acceleration is 200 rpm / s to 2000 rpm / s, and can be optionally 800 rpm / s to 1200 rpm / s; The second rotation speed is 3000 rpm to 4500 rpm, and can be optionally 3800 rpm to 4200 rpm; the spin coating is performed at the second rotation speed for 18 s to 22 s.
26. An electrical device, characterized in that: It comprises at least one of the perovskite-based tandem solar cells described in any one of claims 1 to 21 and the perovskite-based tandem solar cells prepared by the preparation method described in any one of claims 22 to 25.
Citation Information
Cited By
Perovskite-based laminated solar cell and preparation method therefor, and electric device
EP4801242A1